Method of manufacturing a semiconductor device
Patent Information
- Application Number
- KR1020260174127
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-17
- Filing Date
- 2026-09-11
- Publication Date
- 2026-09-22
Smart Images

Figure P1020260174127_ABST
Abstract
Description
Technology Field
[0001] Related applications
[0002] This application claims priority to U.S. Provisional Application No. 63 / 402,851, filed on August 31, 2022, the full text of which is incorporated herein by reference. Background Technology
[0003] As consumer devices are becoming increasingly smaller in response to consumer demands, the size of their individual components is also inevitably decreasing. Semiconductor devices, which constitute the main components of devices such as mobile phones and computer tablets, have been pressured to become smaller, along with corresponding pressure for individual components within the device (e.g., transistors, resistors, capacitors, etc.) to also decrease in size.
[0004] One possible technique used in the manufacturing process of semiconductor devices is the use of photolithography materials. These materials are applied to the surface of a layer to form a pattern, and then exposed to the patterned energy. This exposure modifies the chemical and physical properties of the exposed area of the photosensitive material. This modification can be utilized to remove one area without removing another, along with the lack of modification in the unexposed area of the photosensitive material.
[0005] However, as the size of individual devices decreases, the process window for photolithography processes is becoming increasingly tight. Likewise, developments in the field of photolithography processes require maintaining the ability to reduce device size and further improvements are needed to meet desired design criteria so that progress toward increasingly smaller components can be sustained. Brief explanation of the drawing
[0006] The present disclosure is best understood from the following detailed description when read in conjunction with the accompanying drawings. It is emphasized that, in accordance with standard industry practice, various features are not depicted in a fixed proportion and are used solely for illustrative purposes. In fact, the dimensions of various features may be increased or decreased at will for the sake of clarity of discussion. FIG. 1 illustrates the process flow of manufacturing a semiconductor device according to an embodiment of the disclosed content. FIGS. 2a and 2b show process steps of sequential operations according to an embodiment of the disclosed content. FIG. 3 shows the process steps of a sequential operation according to an embodiment of the disclosed content. FIG. 4 shows the process steps of a sequential operation according to an embodiment of the disclosed content. FIGS. 5a and 5b show the process steps of a sequential operation according to an embodiment of the disclosed content. FIG. 6 shows the process steps of a sequential operation according to an embodiment of the disclosed content. FIGS. 7a and 7b show the process steps of a sequential operation according to an embodiment of the disclosed content. FIG. 8 shows the process steps of a sequential operation according to an embodiment of the disclosed content. FIGS. 9a and 9b show the process steps of a sequential operation according to an embodiment of the disclosed content. FIGS. 10a and 10b show process steps of sequential operations according to an embodiment of the disclosed content. FIGS. 11a and 11b show process steps of sequential operations according to an embodiment of the disclosed content. FIGS. 12a and 12b show process steps of sequential operations according to an embodiment of the disclosed content. FIGS. 13a and 13b show process steps of sequential operations according to an embodiment of the disclosed content. FIGS. 14a and 14b show process steps of sequential operations according to an embodiment of the disclosed content. FIG. 15 illustrates a polymer for a lower layer composition according to an embodiment of the disclosure. FIG. 16 illustrates a polymer for a lower layer composition according to an embodiment of the disclosure. FIG. 17 illustrates a polymer for a lower layer composition according to an embodiment of the disclosure. FIGS. 18a, 18b, and 18c illustrate a polymer for a lower layer composition according to an embodiment of the disclosure. FIG. 19 illustrates an intermediate layer additive according to an embodiment of the disclosed content. FIG. 20 illustrates a photocatalytic cation intermediate layer additive according to an embodiment of the disclosed content. FIG. 21 illustrates a photocatalytic anion intermediate layer additive according to an embodiment of the disclosed content. FIG. 22 illustrates an intermediate layer additive for a light-generating agent according to an embodiment of the disclosed content. FIG. 23 illustrates a silicon-containing monomer according to an embodiment of the disclosed content. FIG. 24 illustrates a silicon-containing monomer according to an embodiment of the disclosed content. FIG. 25 shows the process steps of a sequential operation according to an embodiment of the disclosed content. FIG. 26 illustrates a silicon-containing monomer containing a photocatalytic agent according to an embodiment of the disclosure. FIGS. 27a and 27b illustrate the polymerization reaction of the components of an intermediate layer according to an embodiment of the disclosure. FIG. 28 illustrates the acid generation reaction of a polymer-bonded photocatalytic agent according to an embodiment of the disclosure. FIG. 29 shows a semiconductor device manufactured by a method according to an embodiment of the disclosure. FIGS. 30a, 30b, 30c, 30d, 30e, 30f, 30g, 30h, 30i, 30j, 30k, 30l, 30m, 30n, 30o, 30p, 30q, and 30r show sequential operations according to embodiments of the disclosed content. Specific details for implementing the invention
[0007] It is understood that the following disclosure provides many different embodiments or examples for carrying out different features of the disclosure. Specific embodiments or examples of components and arrangements are described below for the sake of simplifying the disclosure. Of course, these are merely examples and are not intended to be limiting. For example, the dimensions of the elements are not limited to the disclosed ranges or values, but will depend on process conditions and / or the desired properties of the device. Furthermore, in the following description, the formation of the first feature on or above the second feature may include embodiments in which the first and second features are formed in direct contact, and may also include embodiments in which an additional feature may be formed interposed between the first and second features so that the first and second features do not come into direct contact. Various features may be arbitrarily drawn in different scales for simplicity and clarity.
[0008] Additionally, spatially relative terms, e.g., "immediately below," "below," "under," "above," "above," etc., may be used for ease of explanation to describe the relationship of one element or feature to another element(s) or feature(s) in the drawings. Spatially relative terms are intended to include a different orientation of the device in addition to the direction depicted in the drawings or in the operation. The device may have a different orientation (rotated 90 degrees or in a different direction), and spatially relative terms used herein may likewise be interpreted accordingly. Also, the term "made" may mean "containing" or "consisting of." The device may have a different orientation (rotated 90 degrees or in a different direction), and spatially relative terms used herein may likewise be interpreted accordingly. Additionally, in the following manufacturing process, there may be one or more additional operations between the described operations, and the order of operations may vary. Materials, compositions, dimensions, processes, and / or operations as described with respect to one embodiment may be used in other embodiments, and detailed descriptions thereof may be omitted. Source / drain area(s) may refer to the source or drain individually or collectively depending on the context.
[0009] As semiconductor device pattern features become increasingly smaller, photoresist pattern resolution is becoming increasingly important. Extreme ultraviolet (EUV) lithography with exposure at 13.5 nm has been used for semiconductor device critical dimensions of less than 20 nm. In chemically amplified resist (CAR), secondary electrons generated by EUV photons activate photoacid generators (PAGs) and photo-decomposable quenchers (PDQs). However, due to the weak absorption of photoresist by 13.5 nm radiation, scum defects may form during EUV lithography. Low EUV photon absorption will result in poor efficiency of PAG / PDQ activation. Undeveloped resist remaining in trenches can cause bridging lines or footing, leading to failure in the transfer of the photoresist pattern to the underlying layer. Additionally, CARs may suffer from resolution, line-edge roughness, and sensitivity (RLS) trade-offs and insufficient etching resistance that result in poor line-width-roughness (LWR) and poor local critical dimension uniformity (LCDU). Embodiments of the disclosure address these drawbacks of CARs and provide improved resolution, line-edge roughness, sensitivity, line-width roughness, local critical dimension uniformity, and etching resistance.
[0010] A three-layer resist is used to provide increased pattern resolution and etch selectivity. The three-layer resist comprises a bottom layer, an intermediate layer, and a photosensitive top layer. The high silicon content of the intermediate layer provides excellent adhesion, low reflectivity, and a high degree of etch selectivity to both the photosensitive top layer and the bottom layer. In some embodiments, the intermediate layer as formed comprises monomers that crosslink when heated, and terminal hydroxyl groups react with Si-O bonds to form high molecular weight polymers. The bottom layer, for example, a bottom anti-reflective coating (BARC) or a spin-on carbon (SOC) coating, is used to planarize the device or to protect semiconductor device features, for example, metal gates, during subsequent processing operations. Embodiments of the present disclosure include methods and materials that reduce scum defects, thereby improving pattern resolution, reducing line width roughness, reducing line edge roughness, and improving semiconductor device yield. An embodiment of the disclosed content makes it possible to effectively expose and pattern a photoresist using an additionally lower exposure dose.
[0011] Embodiments of the disclosure include a photogenerator (PAG) within an intermediate layer containing a silicon-containing material. In some embodiments, the PAG is a cationic onium group. In some embodiments, the PAG is bonded to a polymer or monomer within the intermediate layer. Upon exposure to actinic radiation, the PAG generates acid within the intermediate layer, and the generated acid subsequently diffuses from the intermediate layer across the intermediate layer / upper layer interface at the exposure plane. The acid diffused into the photosensitive upper layer reacts with the resist polymer and reduces scum defects. Additionally, the acid diffused from the intermediate layer replenishes the photogenerated acid within the upper layer, thereby reducing the exposure dose required for complete exposure of the photosensitive layer. A lower required exposure dose increases the number of wafers per hour (WPH) that can be processed during a lithography operation, which leads to higher device yield and increased device manufacturing efficiency.
[0012] An embodiment of the disclosure comprises a silicon-containing material and a chemical radiation absorbing additive having an iodine substituent within an intermediate layer. Upon exposure to chemical radiation, the chemical radiation absorbing additive absorbs the chemical radiation and generates secondary electrons within the intermediate layer, which subsequently diffuse from the intermediate layer to the exposure plane across the intermediate layer / upper layer interface. The secondary electrons diffusing to the photosensitive upper layer activate a photo-generating agent or photodegradable quencher (PDQ) within the photosensitive layer, thereby reducing the exposure dose required for complete exposure of the photosensitive layer. The lower required exposure dose increases the number of wafers per hour (WPH) that can be processed during a lithography operation, which results in a higher device yield and increased device manufacturing efficiency.
[0013] An embodiment of the disclosure comprises a silicon-containing material within an intermediate layer and a silicon-containing monomer having iodine or phenolic group substituents. The iodine and phenolic group substituents provide increased chemical radiation absorption and improve the crosslinking ability of the monomer. Upon exposure to chemical radiation, the silicon-containing monomer absorbs the chemical radiation and generates secondary electrons within the intermediate layer, which subsequently diffuse from the intermediate layer to the exposure plane across the intermediate layer / upper layer interface. The secondary electrons diffusing to the photosensitive upper layer activate a photo-generating agent or photodegradable quencher (PDQ) within the photosensitive layer, thereby reducing the exposure dose required for complete exposure of the photosensitive layer. The lower required exposure dose increases the number of wafers per hour (WPH) that can be processed during a lithography operation, which leads to higher device yield and increased device manufacturing efficiency. Additionally, the silicon-containing monomer can crosslink with the silicon-containing material and other silicon-containing monomers to reinforce the intermediate layer. In some embodiments, the silicon-containing monomer has a lower density than the silicon-containing material and other components of the intermediate layer, and the silicon-containing monomer floats on the surface of the intermediate layer. In other embodiments, the silicon-containing monomer has a higher density than or nearly the same density as other intermediate layer components.
[0014] In some embodiments, the intermediate layer comprises one or more of a photogenerator, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent. For example, in some embodiments, the intermediate layer comprises a photogenerator and a chemical radiation absorbing additive. In other embodiments, the intermediate layer comprises a photogenerator and a silicon-containing monomer, and in yet another embodiment, the intermediate layer comprises a radiation absorbing additive and a silicon-containing monomer. In some embodiments, the intermediate layer comprises a photogenerator, a chemical radiation absorbing additive, and a silicon-containing monomer.
[0015] FIG. 1 illustrates a process flow (100) for manufacturing a semiconductor device according to an embodiment of the disclosure. A first layer (or lower layer) composition is coated onto the surface of a substrate in operation (S105) to form a first (or lower) layer (110) as shown in FIG. 2a. In some embodiments, the substrate has device features formed thereon as shown in FIG. 2b. In some embodiments, the lower layer (110) is a lower anti-reflective coating (BARC) layer or a planarization layer. In some embodiments, the lower layer (110) is a spin-on carbon layer. In some embodiments, the lower layer (110) has a thickness in the range of about 10 nm to about 2,000 nm. In some embodiments, the thickness of the lower layer is in the range of about 200 nm to about 1,500 nm. A lower layer thickness less than the disclosed range may not provide sufficient protection of the semiconductor device features from subsequent processing operations or may not provide sufficient planarization. A lower layer thickness exceeding the disclosed range may be unnecessarily thick and may not provide any additional meaningful protection or planarization of the lower device feature. In some embodiments, the lower feature includes a transistor having a pin structure or a gate structure. In some embodiments, the lower feature includes a conductive layer (105), for example, a metal layer.
[0016] In some embodiments, the lower layer (110) undergoes a first baking operation (S110) to evaporate the solvent or harden the lower layer composition. In some embodiments, the baking operation (S110) crosslinks the lower layer composition. The lower layer (110) is baked at a temperature and time sufficient to harden and dry the lower layer (110). In some embodiments, the lower layer is heated at a temperature in the range of about 40°C to about 400°C for about 10 seconds to about 10 minutes. In other embodiments, the lower layer (110) is heated at a temperature in the range of about 100°C to about 400°C. In other embodiments, the lower layer (110) is heated at a temperature in the range of about 250°C to about 350°C. In other embodiments, the lower layer (110) is heated at a temperature in the range of about 200°C to about 300°C. Heating the lower layer at a temperature below the disclosed range may cause insufficient curing or crosslinking, and heating the lower layer at a temperature above the disclosed range may cause damage to the lower layer and lower device features. In some embodiments, the curing operation (S110) is performed by exposing the lower layer to chemical radiation. In some embodiments, the chemical radiation is ultraviolet radiation. In some embodiments, the ultraviolet radiation has a wavelength in the range of about 100 nm to less than about 300 nm.
[0017] In some embodiments, the capillary force between the lower layer composition and the substrate (10) or the conductive layer (105) enhances the gap filling of the lower layer composition. Polar groups of the polymer in the lower layer composition may interact with the substrate (10) or the patterned target layer, for example, the conductive layer (105), which can enhance the gap filling.
[0018] The second layer (or intermediate layer) composition is coated onto the surface of the lower layer (110) in operation (S115) to form the second (or intermediate) layer (115) as illustrated in FIG. 3. The intermediate layer (115) may have a composition that provides anti-reflective properties or hard mask properties for photolithography operations. In some embodiments, the intermediate layer (115) has relatively high etching selectivity to both the lower layer and the upper layer, and the intermediate layer (115) provides excellent adhesion to both the lower layer and the upper layer. In some embodiments, the intermediate layer (115) comprises a silicon-containing material (e.g., a silicon hard mask material). The intermediate layer (115) may comprise spin-on glass or a siloxane, a siloxane oligomer, and a polymer (e.g., a polysiloxane). In some embodiments, the intermediate layer composition comprises a silicon-containing monomer, a photogenerator, a silicon-containing monomer having a combined photogenerator group, a silicon-containing polymer having a combined photogenerator, a chemical radiation absorbing additive, or a combination thereof. In some embodiments, the chemical radiation absorbing additive has one or more iodines as substituents and has high absorption of extreme ultraviolet radiation.
[0019] In some embodiments, the intermediate layer (115) has a thickness in the range of about 10 nm to about 500 nm. In some embodiments, the thickness of the intermediate layer (115) is in the range of about 20 nm to about 200 nm. In some embodiments, the ratio of the thickness of the lower layer to the thickness of the intermediate layer is in the range of about 1:1 to about 200:1. An intermediate layer thickness less than the disclosed range may not provide sufficient adhesion or etching resistance. An intermediate layer thickness greater than the disclosed range may be unnecessarily thick and may not provide any additional significant adhesion or etching resistance.
[0020] The intermediate layer (115) undergoes a second baking operation (S120) to evaporate the solvent in some embodiments or to cure the intermediate layer composition. In some embodiments, the second baking operation (S120) induces a reaction between a compound having a photogenerator group and a silicon-containing compound. In some embodiments, the second baking operation (S120) induces polymerization or crosslinking of a silicon-containing monomer having an iodine or phenol substituent, a silicon-containing monomer having a photogenerator group, and other silicon-containing monomers, oligomers, or polymers. The intermediate layer (115) is heated at a temperature in the range of about 40°C to about 400°C for about 10 seconds to about 10 minutes. In other embodiments, the intermediate layer (115) is heated at a temperature in the range of about 150°C to about 400°C, and in other embodiments, the intermediate layer is heated at a temperature in the range of about 200°C to about 300°C. Heating the intermediate layer at a temperature below the disclosed range may cause insufficient curing or cross-linking, and heating the intermediate layer at a temperature above the disclosed range may cause damage to the intermediate layer and underlying device features.
[0021] In some embodiments, the photosensitive upper layer (120) is formed by coating a resist composition onto the intermediate layer (115) in operation (S125) as illustrated in FIG. 4. In some embodiments, the photosensitive layer (120) is a photoresist layer. The lower layer (110), the intermediate layer (115), and the photosensitive (or upper) layer (120) together constitute a three-layer resist (125). Then, the photoresist layer (120) undergoes a third baking operation (S130) (or pre-exposure baking) to evaporate the solvent in the resist composition in some embodiments. The photosensitive layer (120) is baked at a temperature and time sufficient to cure and dry the photosensitive layer (120). In some embodiments, the photosensitive layer is heated at a temperature in the range of about 40°C to about 120°C for about 10 seconds to about 10 minutes.
[0022] After the pre-exposure baking operation (S130) of the photoresist layer (120), the photoresist layer (120) and the intermediate layer (115) are selectively exposed to chemical radiation (45 / 97) (see FIG. 5a and 5b) in operation (S135) (or exposed in a patterned manner). In some embodiments, the photoresist layer (120) and the intermediate layer are selectively exposed to ultraviolet radiation. In some embodiments, the radiation is electromagnetic radiation, for example, g-lines (wavelength of about 436 nm), i-lines (wavelength of about 365 nm), ultraviolet radiation, deep ultraviolet radiation, extreme ultraviolet radiation, electron beams, etc. In some embodiments, the radiation source is selected from the group consisting of a mercury vapor lamp, a xenon lamp, a carbon arc lamp, KrF excimer laser light (wavelength of 248 nm), ArF excimer laser light (wavelength of 193 nm), F2 excimer laser light (wavelength of 157 nm), or CO2 laser-excited Sn plasma (extreme ultraviolet, wavelength of 13.5 nm).
[0023] As illustrated in FIG. 5a, exposure radiation (45) passes through a photomask (30) before irradiating the photoresist layer (120) and the intermediate layer (115) in some embodiments. In some embodiments, the photomask (30) has a pattern to be replicated in the photoresist layer (120). In some embodiments, the pattern is formed on the photomask substrate (40) by an opaque pattern (35). The opaque pattern (35) may be formed by a material opaque to ultraviolet radiation, for example, chromium, and the photomask substrate (40) may be formed by a material transparent to ultraviolet radiation, for example, fused quartz.
[0024] In some embodiments, selective exposure of the photoresist layer (120) and the intermediate layer (115) forming the exposed area (50, 115a) and the unexposed area (52, 115) is performed using extreme ultraviolet lithography. In the extreme ultraviolet lithography operation, a reflective photomask (65) is used to form patterned exposure light in some embodiments as shown in FIG. 5b. The reflective photomask (65) comprises a low thermal expansion glass substrate (70) on which a reflective multilayer (75) of Si and Mo is formed. A capping layer (80) and an absorbent layer (85) are formed on the reflective multilayer (75). A back conductive layer (90) is formed on the back side of the low thermal expansion glass substrate (70). In extreme ultraviolet lithography, extreme ultraviolet radiation (95) is directed toward the reflective photomask (65) at an angle of incidence of about 6°. A portion (97) of the extreme ultraviolet radiation is reflected by the Si / Mo multilayer (75) toward the photoresist-coated substrate (10), and a portion of the extreme ultraviolet radiation incident on the absorber layer (85) is absorbed by the photomask. In some embodiments, additional optics, including a mirror, are present between the reflective photomask (65) and the photoresist-coated substrate.
[0025] In the region (50) of the photoresist layer exposed to radiation, a chemical reaction proceeds, thereby changing its solubility in the subsequently applied developer compared to the region (52) of the photoresist layer not exposed to radiation. In some embodiments, chemical radiation causes a photogenerator to generate acid in a portion of the intermediate layer (115) exposed to radiation. In some embodiments, chemical radiation causes a photogenerator to generate acid in the photoresist layer (120). In some embodiments, the anion or cation of the photogenerator compound in the photoresist layer (120) is different from the anion or cation of the photogenerator in the intermediate layer (115). In some embodiments, chemical radiation causes a chemical radiation absorbing additive having an iodine substituent or other iodine-containing molecule, for example, a cross-linked silicon-containing monomer, to generate secondary electrons.
[0026] Next, the third layer resist (125) undergoes a fourth baking (or post-exposure baking (PEB)) in operation (S140). In some embodiments, the photosensitive layer (120) and the intermediate layer (115) are heated at a temperature ranging from about 50°C to about 160°C for about 20 seconds to about 120 seconds. Post-exposure baking may be used to assist in the generation, dispersion, and reaction of acid or quencher generated from the impact of radiation (45 / 97) on the photoresist layer (120) and the intermediate layer (115) during exposure. The post-exposure baking operation (S140) assists in the diffusion of acid generated in the intermediate layer (115a) from the portion of the intermediate layer (115a) exposed to chemical radiation to the exposed portion (50) of the photoresist layer (120). This assistance helps to generate or enhance a chemical reaction, which creates a chemical difference between the exposed area (50) and the unexposed area (52) within the photoresist layer, thereby improving the resolution of the subsequently developed pattern and reducing the resist scum that would otherwise occur at the bottom of the photoresist layer (120).
[0027] The selectively exposed photoresist layer is subsequently developed in operation (S145) by applying a developer to the selectively exposed photoresist layer. As illustrated in FIG. 6, the developer (57) is supplied from a dispenser (62) to the selectively exposed photoresist layer (120). In some embodiments, the photoresist is a positive tone resist, and the exposed area (50) of the photoresist layer is removed by the developer (57) forming a pattern (55) of openings in the photoresist layer (120) as illustrated in FIG. 7a, thereby exposing the intermediate layer (115a). In another embodiment, the photoresist is a negative tone resist, and as shown in FIG. 7b, the unexposed area (52) of the photoresist layer is removed by a developer (57) that forms a pattern (55') of openings in the photoresist layer (120) to expose the intermediate layer (115a).
[0028] In some embodiments, an opening or pattern (55, 55') in the photoresist layer is extended through the intermediate layer (115) and the lower layer (110) in operation (S150) using an etching solution optionally suitable for each layer as shown in FIG. 8 to form an extended opening or pattern (55"). In some embodiments, the exposed portion of the substrate (10) in the extended opening or pattern (55') is removed using a suitable etching operation as shown in FIG. 9a. In other embodiments, the target layer to be patterned is formed on the substrate, for example, the conductive layer (105) (see FIG. 2b), and the exposed portion of the target layer (105) is removed using a suitable etching technique as shown in FIG. 9b. The photoresist layer (120), the intermediate layer (115), and the lower layer (110) are subjected to a suitable photoresist stripping, etching, or plasma ashing operation as shown in FIG. 10a and 10b. It is subsequently removed in the operation (S155) using. In another embodiment, the pattern (55) of the photoresist layer (120) is extended to the intermediate layer (115) to form a patterned intermediate layer, after which the photoresist layer (120) is removed, and then the lower layer (110) and the lower layer (10, 105) are patterned using the patterned intermediate layer as an etching mask.
[0029] In another embodiment, a target layer (145), for example, an interlayer insulating film (ILD) layer, is formed on the substrate (10) or a feature disposed on the substrate. As shown in FIGS. 11a and 11b, a three-layer resist (125) is formed on the target layer (145) using the material and process described herein, and an opening (140) is formed in the three-layer resist (125). In some embodiments, as shown in FIGS. 12a and 12b, the photoresist layer (120) is removed by a suitable photoresist stripping or plasma ashing process. Then, as shown in FIGS. 13a and 13b, an intermediate layer (115) is used as a hard mask to extend the opening (140) to the ILD layer (145) to form an opening (140') that is exposed to the substrate (10) or the conductive layer (105). As illustrated in FIGS. 13a and 13b, after the formation of the opening (140'), the intermediate layer and the lower layer are removed by suitable operations, e.g., etching and plasma ashing. In some embodiments, as illustrated in FIGS. 14a and 14b, a conductive contact (150) is formed from the opening by subsequently filling the opening (140') with a conductive material by a suitable deposition technique. In some embodiments, the deposition technique includes electroplating, chemical vapor deposition (CVD), physical vapor deposition (PVD), or atomic layer deposition (ALD) techniques. In some embodiments, the conductive contact (150) is formed from one or more metals selected from tungsten, copper, nickel, titanium, tantalum, aluminum, and alloys thereof. In some embodiments, a planarization operation, e.g., chemical mechanical polishing or etch back operation, is performed to remove the metal deposited on the upper surface of the ILD layer (145).
[0030] In some embodiments, the substrate (10) comprises a single-crystal semiconductor layer on at least a surface portion thereof. The substrate (10) may comprise a single-crystal semiconductor material, for example, but not limited to Si, Ge, SiGe, GaAs, InSb, GaP, GaSb, InAlAs, InGaAs, GaSbP, GaAsSb, and InP. In some embodiments, the substrate (10) is a silicon layer of a silicon-on-insulator (SOI) substrate. In certain embodiments, the substrate (10) is made of crystalline Si.
[0031] The substrate (10) may include one or more buffer layers (not shown) in its surface region. The buffer layers may serve to gradually change the lattice constant from that of the substrate to that of the subsequently formed source / drain region. The buffer layers may be formed from epitaxially grown single-crystal semiconductor materials, for example, but not limited to Si, Ge, GeSn, SiGe, GaAs, InSb, GaP, GaSb, InAlAs, InGaAs, GaSbP, GaAsSb, GaN, and InP. In an embodiment, the silicon germanium (SiGe) buffer layer is epitaxially grown on the silicon substrate (10). The germanium concentration of the SiGe buffer layer may increase from 30 atomic% in the bottom buffer layer to 70 atomic% in the top buffer layer.
[0032] In some embodiments, the substrate (10) is at least one metal, metal alloy, and formula MX a It comprises one or more layers of metal nitride / sulfide / oxide / silicon, wherein M is a metal, X is N, S, Se, O, Si, and a is about 0.4 to about 2.5. In some embodiments, the substrate (10) comprises titanium, aluminum, cobalt, ruthenium, titanium nitride, tungsten nitride, tantalum nitride, and combinations thereof.
[0033] In some embodiments, the substrate (10) is at least silicon or formula MXb A dielectric having a metal oxide or nitride is included, wherein M is a metal or Si, X is N or O, and b is in the range of about 0.4 to about 2.5. In some embodiments, the substrate (10) comprises silicon dioxide, silicon nitride, aluminum oxide, hafnium oxide, lanthanum oxide, and combinations thereof.
[0034] FIG. 15 illustrates some components of the lower layer, BARC, planarization layer, or spin-on carbon layer (lower layer) composition according to some embodiments of the disclosure. In some embodiments, the lower layer composition comprises organic polymers including, but not limited to, polyhydroxystyrene, polyacrylate, polymethacrylate, polyvinylphenol, polystyrene, and copolymers thereof. In some embodiments, the organic polymer is poly(4-hydroxystyrene), poly(4-vinylphenol-co-methyl methacrylate) copolymer, and poly(styrene)-b-poly(4-hydroxystyrene) copolymer, as shown in FIG. 15.
[0035] In some embodiments, the lower layer composition comprises a carbon backbone polymer, a first crosslinking agent, and a second crosslinking agent.
[0036] In some embodiments, the first crosslinking agent is A-(OR) x , A-(NR) x ,
[0037] One or more crosslinking agents selected from the group consisting of, wherein A is a monomer, oligomer, or second polymer having a molecular weight in the range of about 100 to about 20,000; R is an alkyl group, cycloalkyl group, cycloalkylepoxy group, or C3-C15 heterocyclic group; OR is an alkyloxy group, cycloalkyloxy group, carbonate group, alkyl carbonate group, alkyl carboxylate group, tosylate group, or mesylate group; NR is an alkylamide group or alkylamino group; and x is in the range of 2 to about 1,000. In some embodiments, the molecular weight of the oligomer or second polymer is the weight-average molecular weight. In some embodiments, R is (CH2) y CH3, where 0 ≤ y ≤ 14. In some embodiments, R is OR is -O(CH2CH2O) a -CH2CH3) where 1 ≤ a ≤ 6. In some embodiments, R, OR, and NR include a chain structure, a ring structure, or a 3D structure. In some embodiments, the 3D structure is selected from the group consisting of norbornyl, adamanthyl, basketanil, twinil, cubanil, and dodecahedranil groups.
[0038] In some embodiments, the second crosslinking agent is A-(OH) x , A-(OR') x , A-(C=C) x , and A-(C≡C) x One or more crosslinking agents selected from the group consisting of, wherein A is a monomer, oligomer, or second polymer having a molecular weight in the range of 100 to 20,000; R' is an alkyloxy group, an alkenyl group, or an alkynyl group; and x is in the range of 2 to about 1,000. In some embodiments, R is (CH2) yCH3, where 0 ≤ y ≤ 14. In some embodiments, R and OR include a chain structure, a ring structure, or a 3D structure. In some embodiments, the 3D structure is selected from the group consisting of norbornyl, adamanthyl, basketanil, twinil, cubanil, and dodecahedranil groups.
[0039] In some embodiments, the carbon backbone polymer contains crosslinking sites on the polymer.
[0040] In some embodiments, the concentrations of the first and second crosslinking agents are in the range of about 20% by weight to about 50% by weight of the total weight of the first and second crosslinking agents and the carbon backbone polymer. In some embodiments, less than about 20% by weight of the crosslinking agent results in insufficient crosslinking. In some embodiments, more than about 50% by weight of the crosslinking agent provides no improvement in crosslinking or provides barely negligible improvement. In some embodiments, the concentration of the first crosslinking agent is in the range of about 5% by weight to about 40% by weight of the total weight of the first and second crosslinking agents and the carbon backbone polymer. In some embodiments, the concentration of the second crosslinking agent is in the range of about 5% by weight to about 40% by weight of the total weight of the first and second crosslinking agents and the carbon backbone polymer. In some embodiments, the concentration of the first crosslinking agent is approximately the same as the concentration of the second crosslinking agent.
[0041] In some embodiments, the lower layer (110) is subjected to a first heating at a temperature in the range of about 100°C to about 170°C to form a partially cross-linked layer. In some embodiments, the first heating is performed at a temperature in the range of about 100°C to about 150°C.
[0042] The viscosity of the underlying layer composition is selected to provide a target thickness when spin-coated onto a substrate. In some embodiments, the underlying layer composition is about 0.1 × 10⁻⁶ at about 20°C. 6 Pa·s to about 1 × 10⁻⁶ 6It has a viscosity of Pa·s and is spin-coated on a substrate at about 1500 rpm. A first heating at about 100°C to about 170°C induces partial polymer crosslinking, and in some embodiments, the viscosity is about 0.1 × 10⁻⁶. 6 Pa·s to about 1 × 10⁻⁶ 6 Approximately 1 × 10⁻⁶ in the Pa·s range 6 Pa·s to about 1 × 10⁻⁶ 8 Increase to Pa·s. A second heating at approximately 170°C to approximately 300°C induces additional polymer crosslinking and increases the viscosity to approximately 1 × 10⁻⁶ 6 Pa·s to about 1 × 10⁻⁶ 8 The solid state layer is increased at Pa·s. A first heating temperature of less than about 100°C may cause insufficient partial crosslinking. A first heating temperature of more than about 170°C may cause negligible additional partial crosslinking or may prematurely trigger a second crosslinking agent. In some embodiments, the lower layer (110) is heated at the first temperature for about 10 seconds to about 5 minutes to partially crosslink the lower layer (110). In some embodiments, the first heating is performed for about 30 seconds to about 3 minutes. In some embodiments, the second heating is performed for about 30 seconds to about 3 minutes.
[0043] After the first heating, the lower layer (110) is allowed to cool for about 10 seconds to about 1 minute at about 20°C to about 25°C in some embodiments. Then, the lower layer (110) is subsequently subjected to a second heating at a second temperature higher than the first temperature to form an additionally or completely cross-linked lower layer (110). In some embodiments, the second temperature is in the range of about 170°C to about 300°C. In some embodiments, the second temperature is in the range of about 180°C to about 300°C. In some embodiments, the second temperature is in the range of about 200°C to about 280°C. At a temperature below about 170°C, the second heating may result in insufficient cross-linking. A second heating temperature above about 300°C or 400°C may result in reflow in the layer or an unacceptable increase in decomposition or degradation of the organic material forming the layer (110). In some embodiments, the layer (110) is heated at a second temperature for about 30 seconds to about 3 minutes. In other embodiments, the second heating is performed for about 30 seconds to about 2 minutes. After the second heating, the lower layer is cooled at about 20°C to about 25°C for about 10 seconds to about 1 minute before performing a subsequent process.
[0044] FIG. 16 illustrates an example of a crosslinking operation in a lower layer (110) according to an embodiment of the disclosure. In an embodiment, the lower layer comprises a main polymer, e.g., polyhydroxystyrene, a low activation energy (Ea) crosslinking agent having four alkoxy crosslinking groups, and a high activation energy (Ea) crosslinking agent having four hydroxyl groups. A low-temperature baking operation is performed on the lower layer, e.g., heating at about 130°C, which triggers the low Ea crosslinking agent to partially crosslink the main polymer. Then, a high-temperature baking operation is performed, e.g., heating at about 250°C, which triggers the high Ea crosslinking agent to more completely crosslink the main polymer.
[0045] In some embodiments, the lower layer is made of a polymer composition comprising a polymer having one or more of the repeating units (1-12) of FIG. 17. In FIG. 17, a, b, c, d, e, f, g, h, and i are each independently H, -OH, -ROH, -R(OH)2, -NH2, -NHR, -NR2, -SH, -RSH, or -R(SH)2, wherein at least one of a, b, c, d, e, f, g, h, and i in each repeating unit (1-12) is not H. R, R1, and R2 are each independently a C1-C10 alkyl group, a C3-C10 cycloalkyl group, a C1-C10 hydroxyalkyl group, a C2-C10 alkoxy group, a C2-C10 alkoxyalkyl group, a C2-C10 acetyl group, a C3-C10 acetylalkyl group, a C1-C10 carboxyl group, a C2-C10 alkyl carboxyl group, or a C4-C10 cycloalkyl carboxyl group, and n is 2 to 1000. A polymer formed from the repeating unit (1-12) of FIG. 17 can be crosslinked when heated or exposed to chemical radiation. In some embodiments, the underlying composition comprises one or more of a crosslinking agent or a coupling reagent. The crosslinking agent crosslinks the underlying composition when heated or exposed to chemical radiation. Examples of repeating units (1-12) according to embodiments of the disclosure are shown in FIG. 18a, 18b, and 18c. In some embodiments, each repeating unit includes two or more functional groups.
[0046] In some embodiments, the polymer comprises repeating units having one or more of hydroxyl groups, amine groups, or mercapto groups. In some embodiments, each repeating unit comprises at least two functional groups selected from one or more of -OH, -ROH, -R(OH)2, -NH2, -NHR, -NR2, -SH, -RSH, or -R(SH)2, wherein R is a C1-C10 alkyl group, a C3-C10 cycloalkyl group, a C1-C10 hydroxyalkyl group, a C2-C10 alkoxy group, a C2-C10 alkoxyalkyl group, a C2-C10 acetyl group, a C3-C10 acetylalkyl group, a C1-C10 carboxyl group, a C2-C10 alkyl carboxyl group, or a C4-C10 cycloalkyl carboxyl group.
[0047] In some embodiments, the lower layer composition comprises a polymer having one or more of the repeating units disclosed in FIG. 17-18c disclosed herein. In some embodiments, at least one repeating unit comprises three or more of -OH, -ROH, -R(OH)2, -NH2, -NHR, -NR2, -SH, -RSH, or -R(SH)2. In some embodiments, the polymer comprises at least one repeating unit having three or more -OH groups.
[0048] In some embodiments, the crosslinking agent has the following structure:
[0049]
[0050] In another embodiment, the crosslinking agent has the following structure:
[0051] ,
[0052] In the above formula, C is a carbon, and n is in the range of 1 to 15; A and B independently comprise a hydrogen atom, a hydroxyl group, a halide, an aromatic carbon ring, or a linear or cyclic alkyl, alkoxyl / fluoro, alkyl / fluoroalkoxyl chain having 1 to 12 carbon atoms, and each carbon C contains A and B; at the first end of the carbon C chain, the first end carbon C comprises X, and at the second end of the carbon chain, the second end carbon C comprises Y, wherein X and Y independently comprise an amine group, a thiol group, a hydroxyl group, an isopropyl alcohol group, or an isopropyl amine group, which is excluded when n=1, in which case X and Y are bonded to the same carbon C. Specific examples of materials that can be used as crosslinking agents include the following:
[0053]
[0054] Alternatively, in some embodiments, a coupling agent is added instead of or in addition to the crosslinking agent added to the underlying composition. The coupling agent assists crosslinking by reacting with groups of the hydrocarbon structure in the polymer before the crosslinking agent, thereby enabling a reduction in the reaction energy of the crosslinking and an increase in the reaction rate. Then, the coupled coupling agent reacts with the crosslinking agent, thereby coupling the crosslinking agent to the polymer.
[0055] Alternatively, in some embodiments where a coupling agent is added to the underlying composition without a crosslinking agent, the coupling agent is used to couple a group from one of the hydrocarbon structures in the polymer to a second group from a distinct hydrocarbon structure in order to crosslink and bond the two polymers together. However, in these embodiments, unlike a crosslinking agent, the coupling agent does not remain as part of the polymer but only assists in directly bonding one hydrocarbon structure to the structure of another hydrocarbon.
[0056] In some embodiments, the coupling reagent has the following structure:
[0057]
[0058] In the above formula, R is a carbon atom, a nitrogen atom, a sulfur atom, or an oxygen atom; M includes a chlorine atom, a bromine atom, an iodine atom, -NO2; -SO3-; -H-; -CN; -NCO, -OCN; -CO2-; -OH; -OR*, -OC(O)CR*; -SR, -SO2N(R*)2; -SO2R*; SOR; -OC(O)R*; -C(O)OR*; -C(O)R*; -Si(OR*)3; -Si(R*)3; an epoxy group, etc.; and R* is a substituted or unsubstituted C1-C12 alkyl, C1-C12 aryl, C1-C12 aralkyl, etc. Specific examples of materials used as coupling reagents in some embodiments include the following:
[0059]
[0060] In some embodiments, the lower layer (110) is formed by preparing a lower layer coating composition of a polymer and any crosslinking agent or coupling reagent in a solvent. The solvent may be any solvent suitable for dissolving the polymer. The lower layer coating composition is applied onto a substrate (10) or device feature, for example, by spin coating. Then, the lower layer composition is baked as described herein to dry the lower layer and crosslink the polymer.
[0061] In some embodiments, the lower layer composition comprises a solvent. In some embodiments, the solvent is selected so that the polymer and additives, for example, a crosslinking agent, can be evenly dissolved in the solvent and dispersed on the substrate.
[0062] In some embodiments, the solvent is an organic solvent and comprises one or more of any suitable solvent, for example, ketone, alcohol, polyalcohol, ether, glycol ether, cyclic ether, aromatic hydrocarbon, ester, propionate, lactate, alkylene glycol monoalkyl ether, alkyl lactate, alkyl alkoxypropionate, cyclic lactone, ring-containing monoketone compound, alkylene carbonate, alkyl alkoxyacetate, alkyl pyruvate, lactate ester, ethylene glycol alkyl ether acetate, diethylene glycol, propylene glycol alkyl ether acetate, alkylene glycol alkyl ether ester, alkylene glycol monoalkyl ester, etc.
[0063] Specific examples of substances that can be used as solvents for the lower layer include acetone, methanol, ethanol, propanol, isopropanol (IPA), n-butanol, toluene, xylene, 4-hydroxy-4-methyl-2-pentanone, tetrahydrofuran (THF), methyl ethyl ketone, cyclohexanone (CHN), methyl isoamyl ketone, 2-heptanone (MAK), ethylene glycol, 1-ethoxy-2-propanol, methyl isobutyl carbinol (MIBC), ethylene glycol monoacetate, ethylene glycol dimethyl ether, ethylene glycol methyl ethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol, diethylene glycol monoacetate, diethylene glycol monomethyl ether, diethylene glycol diethyl ether, and diethylene glycol dimethyl Ether, Diethylene Glycol Ethylmethyl Ether, Diethylene Glycol Monoethyl Ether, Diethylene Glycol Monobutyl Ether, Ethyl 2-Hydroxypropionate, Methyl 2-Hydroxy-2-Methylpropionate, Ethyl 2-Hydroxy-2-Methylpropionate, Ethyl Ethoxyacetate, Ethyl Hydroxyacetate, Methyl 2-Hydroxy-2-Methylbutanate, Methyl 3-Methoxypropionate, Ethyl 3-Methoxypropionate, Methyl 3-Ethoxypropionate, Ethyl 3-Ethoxypropionate, Methyl Acetate, Ethyl Acetate, Propyl Acetate, n-Butyl Acetate (nBA), Methyl Lactate, Ethyl Lactate (EL), Propyl Lactate, Butyl Lactate, Propylene Glycol, Propylene Glycol Monoacetate, Propylene Glycol Monoethyl Ether Acetate, propylene glycol monomethyl ether acetate, propylene glycol monopropyl methyl ether acetate, propylene glycol monobutyl ether acetate, propylene glycol monomethyl ether propionate, propylene glycol monoethyl ether propionate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, ethylene glycol monomethyl ether acetate,Ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl 3-methoxypropionate, methyl 3-ethoxypropionate, and ethyl 3-methoxypropionate, β-propiolactone, β-butyrolactone, γ-butyrolactone (GBL), α-methyl-γ-butyrolactone, β-methyl-γ-butyrolactone, γ-valerolactone, γ-caprolactone, γ-octanoic lactone, α-hydroxy-γ-butyrolactone, 2-butanone, 3-methylbutanone, pinacolone, 2-pentanone, 3-pentanone, 4-methyl-2-pentanone, 2-methyl-3-pentanone, 4,4-dimethyl-2-pentanone, 2,4-dimethyl-3-pentanone, 2,2,4,4-tetramethyl-3-pentanone, 2-hexanone, 3-hexanone, 5-methyl-3-hexanone, 3-heptanone, 4-heptanone, 2-methyl-3-heptanone, 5-methyl-3-heptanone, 2,6-dimethyl-4-heptanone, 2-octanone, 3-octanone, 2-nonanone, 3-nonanone, 5-nonanone, 2-decanone, 3-decanone, 4-decanone, 5-hexen-2-one, 3-penten-2-one, cyclopentanone, 2-methylcyclopentanone, 3-methylcyclopentanone, 2,2-Dimethylcyclopentanone, 2,4,4-Trimethylcyclopentanone, 3-Methylcyclohexanone, 4-Methylcyclohexanone, 4-Ethylcyclohexanone, 2,2-Dimethylcyclohexanone, 2,6-Dimethylcyclohexanone, 2,2,6-Trimethylcyclohexanone, Cycloheptanone, 2-Methylcycloheptanone, 3-Methylcycloheptanone, Propylene Carbonate, Vinylene Carbonate, Ethylene Carbonate, Butylene Carbonate, Acetate-2-Methoxyethyl, Acetate-2-Ethoxyethyl, Acetate-2-(2-Ethoxyethoxy)ethyl, Acetate-3-Methoxy-3-Methylbutyl, Acetate-1-Methoxy-2-Propyl, Dipropylene Glycol Monomethyl Ether, Monoethyl Ether, Monopropyl Ether, Monobutyl Ether, Monophenyl ether, dipropylene glycol monoacetate, dioxane, methyl pyruvate, ethyl pyruvate, propyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate,Includes n-methylpyrrolidone (NMP), 2-methoxyethyl ether (Diglym), ethylene glycol monomethyl ether, methyl propionate, ethyl propionate, ethyl 3-ethoxypropionate, propylene glycol methyl ether acetate (PGMEA), methylene cellosolve, 2-ethoxyethanol, N-methylformamide, N,N-dimethylformamide (DMF), N-methylformanilide, N-methylacetamide, N,N-dimethylacetamide, dimethyl sulfoxide, benzyl ethyl ether, dihexyl ether, acetonylacetone, isophorone, caproic acid, caprylic acid, 1-octanol, 1-nonanol, benzyl alcohol, benzyl acetate, ethyl benzoate, diethyl oxalate, diethyl maleate, phenyl cellosolve acetate, etc.
[0064] In some embodiments, the intermediate layer (115) comprises a silicon-containing layer (e.g., a silicon hard mask material). The intermediate layer (115) may comprise a silicon-containing organic or inorganic polymer. In other embodiments, the intermediate layer comprises a siloxane polymer. In other embodiments, the intermediate layer (115) comprises silicon oxide (e.g., spin-on glass (SOG)), silicon nitride, silicon oxynitride, polycrystalline silicon; and / or other suitable materials. The intermediate layer (115) may be bonded to adjacent layers (e.g., a lower layer (110) and an upper layer (120)) by, for example, covalent bonding, hydrogen bonding, or hydrophilic-to-hydrophilic force. Thus, the intermediate layer (115) may comprise a composition that allows for covalent bonding to be formed between the intermediate layer (115) and the superimposed photoresist layer (120) after an exposure process and / or a subsequent baking process.
[0065] In some embodiments, the intermediate layer (115) comprises a chemical radiation absorbing additive having an iodine substituent. In some embodiments, the intermediate layer (115) is structure I nA chemical radiation absorbing additive having -R1, wherein n = 1-10, and R1 is selected from the group consisting of substituted or unsubstituted C1-C10 alkyl groups, C6-C10 aryl groups, C1-C10 aralkyl groups, C3-C10 cycloalkyl groups, C1-C10 hydroxyalkyl groups, C2-C10 alkoxyalkyl groups, C2-C10 acetyl groups, C3-10 acetylalkyl groups, C1-C10 carboxyl groups, C2-C10 alkyl carboxyl groups, C3-C10 cycloalkyl carboxyl groups, or adamantyl groups. In some embodiments, the chemical radiation absorbing additive having an iodine substituent is one or more of the compounds of FIG. 19.
[0066] In some embodiments, the intermediate layer (115) It includes a component having a photogenerator (PAG). The PAG interacts with the exposed photoresist layer (120) to generate acid. In some embodiments, the PAG is bonded to a silicon-containing material in an intermediate layer. In some embodiments, the intermediate layer (115) comprises a polysiloxane having a pendant PAG group. In some embodiments, the PAG comprises one or more chemical radiation-absorbing substituents, for example, iodine. In some embodiments, the photogenerator comprises an anion and a cation. In some embodiments, the photogenerator comprises a cation bonded to a silicon-containing material or a silicon-containing monomer. In some embodiments, the cation is an onium, including iodine or a sulfonium cation. In some embodiments, the anion or cation comprises one or more chemical radiation-absorbing substituents, for example, iodine. In some embodiments, the sulfonium is triphenylsulfonium. In some embodiments, the anion is a sulfite anion. In some embodiments, the anion is a sulfite anion having an organic group substituent. In some embodiments, the anion comprises a fluorocarbon substituent. In some embodiments, the PAG comprises one of the cations of FIG. 20. In some embodiments, the PAG comprises one of the anions of FIG. 21. In some embodiments, the PAG is one of the anion / cation pairs of FIG. 22.
[0067] In some embodiments, the intermediate layer (115) comprises a silicon-containing monomer having an iodine or phenol group substituent. In some embodiments, the silicon-containing monomer has the following structure:
[0068]
[0069] In the above formula, Z and D are independently substituted or unsubstituted C1-C20 alkyl groups, C3-C20 cycloalkyl groups, C1-C20 hydroxyalkyl groups, C2-C20 alkoxy groups, C3-C20 alkoxyalkyl groups, C2-C20 acetyl groups, C3-C20 acetyl alkyl groups, C1-C20 carboxyl groups, C2-C20 alkyl carboxyl groups, C1-C20 alkyl fluoride groups, C6-C20 aryl groups, C7-C20 aralkyl groups, or adamantyl groups, wherein Z and D independently comprise 1-10 iodine or 1-10 phenol OH groups, Z is a single bond, and D is H; R4, R5, and R6 are each H or a substituted or unsubstituted C6-C20 aryl group, C7-C20 aralkyl group, C3-C20 cycloalkyl group, C1-C20 hydroxyalkyl group, C2-C20 alkoxy group, C3-C20 alkoxyalkyl group, C2-C20 acetyl group, C3-C20 acetylalkyl group, C1-C20 carboxyl group, C2-C20 alkyl carboxyl group, or C4-C20 cycloalkyl carboxyl group. In some embodiments, the silicon-containing monomer comprises one or more of the compounds of FIG. 23 and 24.
[0070] In some embodiments, the intermediate layer (115) contains about 30 weight% to about 99 weight% of silicon-containing material based on the total solid weight of the intermediate layer (115). In some embodiments, the concentration of silicon-containing material in the intermediate layer is in the range of about 50 weight% to about 75 weight%. In some embodiments, the intermediate layer (115) contains about 1 weight% to about 70 weight% of a chemical radiation absorbing additive, a component having PAG, or a silicon-containing monomer based on the total solid weight of the intermediate layer (115). In some embodiments, the concentration of the chemical radiation absorbing additive, the component having PAG, or the silicon-containing monomer in the intermediate layer (115) is in the range of about 25 weight% to about 50 weight%. At concentrations outside these ranges, there may not be a sufficient amount of the component to obtain a beneficial effect of the component, or there may not be any significant improvement in the beneficial effect.
[0071] In some embodiments, the intermediate layer composition comprises a solvent. The solvent may be any solvent discussed herein used to form the lower layer. In some embodiments, the intermediate layer (115) is formed on the lower layer (110) by spin coating. In some embodiments, as illustrated in FIG. 25, during spin coating, the silicon-containing monomer is separated from the intermediate layer composition and floats on top of other components (e.g., solvent and silicon-containing material) in the intermediate layer composition forming the upper intermediate layer (115b) and the lower intermediate layer (115a). When the intermediate layer is subsequently heated, the upper intermediate layer (115b) is cross-linked in some embodiments.
[0072] In some embodiments, the silicon-containing monomer has a density greater than or approximately equal to that of other intermediate layer components. These silicon-containing monomers do not float on the upper surface of other intermediate layer components. FIG. 23 illustrates some non-floating silicon-containing monomers according to an embodiment of the disclosure. In other embodiments, the silicon-containing monomer has a density smaller than that of other components of the intermediate layer composition. Silicon-containing monomers having a lower density can be separated during spin coating and float on the upper surface of other intermediate layer components. FIG. 24 illustrates some floating silicon-containing monomers according to an embodiment of the disclosure.
[0073] A silicon-containing monomer having a PAG group according to some embodiments is as follows:
[0074]
[0075] In the above formula, A is a direct bond, a C1-C5 alkyl group, a C1-C5 cycloalkyl group, a C1-C5 hydroxyalkyl group, a C1-C5 alkoxy group, a C1-C5 alkoxylalkyl group, a C1-C5 acetyl group, a C1-C5 acetylalkyl group, a C1-C5 carboxyl group, or a C1-C5 alkyl carboxyl group; R1 and R2 are each independently a C6-C12 aryl group, C6-C12 alkyl group, C6-C12 cycloalkyl group, C6-C12 hydroxyalkyl group, C6-C12 alkoxy group, C6-C12 alkoxylalkyl group, C6-C12 acetyl group, C6-C12 acetylalkyl group, C6-C12 carboxyl group, C6-C12 alkyl carboxyl group, C6-C12 cycloalkyl carboxyl group, C3-C15 saturated or unsaturated hydrocarbon ring or C2-C15 heterocyclic group; R3 is a C1-C20 fluorocarbon group, C6-C20 aryl group, or C10-C20 adamantyl group; and a, b, d, and d are each independently H or a C1-C6 alkyl group. In some embodiments, R1, R2, and R3 independently contain 1 to 3 iodine atoms.
[0076] FIG. 28 illustrates an acid generation reaction according to some embodiment of the disclosure. A photogenerator comprising cations and anions is bonded to a polymer. The cationic polymer bonded to the PAG does not extend to the photosensitive layer (120) because it is bonded to the intermediate layer polymer during the photoresist coating process. When exposed to chemical radiation, the anion (acid) detaches from the PAG group. After exposure to chemical radiation, the generated acid is released and diffuses into the photosensitive layer. A subsequent post-exposure baking operation (S140) accelerates the diffusion of the acid into the exposed portion of the photosensitive layer (120).
[0077] In some embodiments, a photogenerator compound is first reacted with a siloxane, and the reaction product, which is a siloxane having a photogenerator group, is applied over the lower layer (110) and then polymerized or crosslinked over the lower layer (110). In some embodiments, the intermediate layer composition is a mixture of spin-on glass (SOG) and a photogenerator. In some embodiments, the photogenerator is first reacted with an SOG precursor, and then the reaction product is applied over the lower layer (110) and cured. In some embodiments, a silicon-containing material and a photogenerator are mixed together, and the mixture is applied to the lower layer. In some embodiments, the mixture is applied over the first layer and then subsequently heated to form a reaction product of the photogenerator and the silicon-containing material. In some embodiments, the reaction product is further heated to induce polymerization or crosslinking of the reaction product. In some embodiments, the PAG bonded to the silicon-containing monomer comprises a chemical radiation-absorbing substituent, for example, iodine. FIG. 26 illustrates several silicon-containing monomers having a bonded PAG according to an embodiment of the disclosure. In some embodiments, the substrate or intermediate layer composition is heated during the spin coating operation, and the intermediate layer composition is polymerized or crosslinked during the application operation.
[0078] In some embodiments, as discussed herein with reference to operation (S115) (Fig. 1), the intermediate layer composition is applied over the lower layer (110), and then the intermediate layer (115) is heated at a temperature ranging from about 150°C to about 400°C. In some embodiments, the intermediate layer (115) is heated at a temperature ranging from about 200°C to about 300°C. The baking operation (S120) induces a reaction, polymerization, or crosslinking of the components of the intermediate layer composition.
[0079] The polymerization reaction of the silicon-containing monomer initiated by the baking operation (S120) according to some embodiments is illustrated in FIG. 27a. As illustrated in FIG. 27b, in some embodiments, a mixture of the silicon-containing monomer (155) and the silicon-containing monomer (160) substituted with a PAG group or a chemical radiation-absorbing substituent is baked under the baking conditions described herein. As a result of the baking, as illustrated in FIG. 27b, in some embodiments, the monomer is polymerized and crosslinked.
[0080] The photosensitive layer (120) is a photoresist layer that is patterned by exposure to chemical radiation in some embodiments. Typically, the chemical properties of the photoresist area struck by incident radiation vary to some extent depending on the type of photoresist used. The photoresist layer (120) is a positive tone resist or a negative tone resist. A positive tone resist refers to a photoresist material that becomes soluble in a developer when exposed to radiation, for example, UV light, and where the unexposed (less exposed) area of the photoresist is insoluble in the developer. On the other hand, a negative tone resist refers to a photoresist material that becomes insoluble in a developer when exposed to radiation, and where the unexposed (less exposed) area of the photoresist is soluble in the developer. The negative resist area that becomes insoluble when exposed to radiation may become insoluble due to a cross-linking reaction induced by exposure to radiation.
[0081] Whether the resist is positive or negative tone will depend on the type of developer used to develop the resist. For example, some positive tone photoresists provide a positive pattern (i.e., the exposed area is removed by the developer) when the developer is an aqueous developer, for example, a tetramethylammonium hydroxide (TMAH) solution. On the other hand, the same photoresists provide a negative pattern (i.e., the unexposed area is removed by the developer) when the developer is an organic solvent. Additionally, in some negative tone photoresists developed with a TMAH solution, the unexposed area of the photoresist is removed by TMAH, and the exposed area of the photoresist, where crosslinking occurs upon exposure to chemical radiation, remains on the substrate after development.
[0082] In some embodiments, a resist composition, e.g., a photoresist according to an embodiment of the disclosure, comprises a polymer or a polymerizable monomer or oligomer together with one or more photoactive compounds (PACs). In some embodiments, the concentration of the polymer, monomer, or oligomer is in the range of about 1 wt% to about 75 wt% based on the total weight of the resist composition. In other embodiments, the concentration of the polymer, monomer, or oligomer is in the range of about 5 wt% to about 50 wt%. At concentrations of the polymer, monomer, or oligomer below the disclosed range, the polymer, monomer, or oligomer has a negligible effect on the resist performance. At concentrations above the disclosed range, there is no substantial improvement in resist performance or a degradation in the formation of a consistent resist layer.
[0083] In some embodiments, the polymerizable monomer or oligomer comprises acrylic acid, acrylate, hydroxystyrene, or alkylene. In some embodiments, the polymer comprises a hydrocarbon structure (e.g., alicyclic hydrocarbon structure) that contains one or more groups to degrade (e.g., acid unstable groups) or otherwise reacts with an acid, base, or free radical generated by a PAC (as further described below). In some embodiments, the hydrocarbon structure comprises repeating units that form the backbone of the polymer resin. These repeating units may include acrylic esters, methacrylic esters, crotonic esters, vinyl esters, maleic diesters, fumaric diesters, itaconic diesters, (meth)acrylonitrile, (meth)acrylamide, styrene, vinyl ethers, combinations thereof, etc.
[0084] In some embodiments, a specific structure used for the repeating unit of the hydrocarbon structure is methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, acetoxyethyl acrylate, phenyl acrylate, 2-hydroxyethyl acrylate, 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-(2-methoxyethoxy)ethyl acrylate, cyclohexyl acrylate, benzyl acrylate, 2-alkyl-2-adamantyl(meth)acrylate or dialkyl(1-adamantyl)methyl(meth)acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, It includes one or more of n-hexyl methacrylate, 2-ethylhexyl methacrylate, acetoxyethyl methacrylate, phenyl methacrylate, 2-hydroxyethyl methacrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, 2-(2-methoxyethoxy)ethyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, 3-chloro-2-hydroxypropyl methacrylate, 3-acetoxy-2-hydroxypropyl methacrylate, 3-chloroacetoxy-2-hydroxypropyl methacrylate, butyl crotonate, hexyl crotonate, etc.Examples of vinyl esters include vinyl acetate, vinyl propionate, vinyl butylate, vinyl methoxyacetate, vinyl benzoate, dimethyl maleate, diethyl maleate, dibutyl maleate, dimethyl fumarate, diethyl fumarate, dibutyl fumarate, dimethyl itaconate, diethyl itaconate, dibutyl itaconate, acrylamide, methyl acrylamide, ethyl acrylamide, propyl acrylamide, n-butyl acrylamide, tert-butyl acrylamide, cyclohexyl acrylamide, 2-methoxyethyl acrylamide, dimethyl acrylamide, diethyl acrylamide, phenyl acrylamide, benzyl acrylamide, methacrylamide, methyl methacrylamide, ethyl methacrylamide, propyl methacrylamide, n-butyl methacrylamide, tert-butyl methacrylamide, cyclohexyl methacrylamide, 2-methoxyethyl methacrylamide, dimethyl methacrylamide, and diethyl Examples of styrene include methacrylamide, phenyl methacrylamide, benzyl methacrylamide, methyl vinyl ether, butyl vinyl ether, hexyl vinyl ether, methoxyethyl vinyl ether, dimethylaminoethyl vinyl ether, etc. Examples of styrene include styrene, methyl styrene, dimethyl styrene, trimethyl styrene, ethyl styrene, isopropyl styrene, butyl styrene, methoxy styrene, butoxy styrene, acetoxy styrene, hydroxy styrene, chloro styrene, dichloro styrene, bromostyrene, vinyl methyl benzoate, α-methyl styrene, maleimide, vinylpyridine, vinylpyrrolidone, vinylcarbazole, combinations thereof, etc.
[0085] In some embodiments, the polymer is polyhydroxystyrene, polymethyl methacrylate, or polyhydroxystyrene-t-butyl acrylate, for example,
[0086] am.
[0087] In some embodiments, to form an alicyclic hydrocarbon structure, the repeating unit of the hydrocarbon structure also has a monocyclic or polycyclic hydrocarbon structure substituted therefor, or the monocyclic or polycyclic hydrocarbon structure is the repeating unit. In some embodiments, specific examples of the monocyclic structure include acycloalkane, tricycloalkane, tetracycloalkane, cyclopentane, cyclohexane, etc. In some embodiments, specific examples of the polycyclic structure include adamantane, norbonane, isobornane, tricyclodecane, tetracyclododecane, etc.
[0088] In addition, a group to be degraded, also known as a leaving group, or an acid instability group in some embodiments where the PAC is a photogenerator, will be attached to the hydrocarbon structure and react with acid / base / free radicals generated by the PAC during exposure. In some embodiments, the group to be degraded is a carboxylic acid group, a fluorinated alcohol group, a phenolic alcohol group, a sulfonic group, a sulfonamide group, a sulfonylimido group, a (alkylsulfonyl)(alkylcarbonyl)methylene group, a (alkylsulfonyl)(alkyl-carbonyl)imido group, a bis(alkylcarbonyl)methylene group, a bis(alkylcarbonyl)imido group, a bis(alkylsulfonyl)methylene group, a bis(alkylsulfonyl)methylene group, a bis(alkylsulfonyl)imido group, a tris(alkylcarbonyl)methylene group, a tris(alkylsulfonyl)methylene group, a combination thereof, etc. In some embodiments, a specific group used for the fluorinated alcohol group includes a fluorinated hydroxyalkyl group, for example, a hexafluoroisopropanol group. A specific group used for the carboxylic acid group includes an acrylic acid group, a methacrylic acid group, etc.
[0089] In some embodiments, the polymer also includes other groups attached to the hydrocarbon structure that help improve various properties of the polymerizable resin. For example, the inclusion of lactone groups in the hydrocarbon structure assists in reducing the amount of line edge roughness after the photoresist is developed, thereby helping to reduce the number of defects occurring during development. In some embodiments, although any suitable lactone structure may alternatively be used for the lactone group, the lactone group comprises a ring having 5 to 7 members.
[0090] In some embodiments, the polymer includes a group that can assist in increasing the adhesion of the photoresist layer (120) to the lower intermediate layer (115). A polar group may be used to help increase adhesion. Although any suitable polar group may be used alternatively, suitable polar groups include hydroxyl groups, cyano groups, etc.
[0091] Optionally, in some embodiments, the polymer comprises one or more alicyclic hydrocarbon structures that do not also contain groups to be degraded. In some embodiments, the hydrocarbon structures that do not contain groups to be degraded include structures such as 1-adamantyl (meth)acrylate, tricyclodecaneyl (meth)acrylate, cyclohexyl (meth)acrylate, and combinations thereof.
[0092] In some embodiments, for example, when EUV radiation is used, the photoresist composition according to the present disclosure is a metal-containing resist. The metal-containing resist comprises a metallic core complexed with one or more ligands in a solvent. In some embodiments, the resist comprises metal particles. In some embodiments, the metal particles are nanoparticles. As used herein, nanoparticles are particles having an average particle size of about 1 nm to about 20 nm. In some embodiments, the metallic core comprising 1 to about 18 metal particles is complexed with one or more organic ligands in a solvent. In some embodiments, the metallic core comprises 3, 6, 9, or more metal nanoparticles complexed with one or more organic ligands in a solvent.
[0093] In some embodiments, the metal particles are one of titanium (Ti), zinc (Zn), zirconium (Zr), nickel (Ni), cobalt (Co), manganese (Mn), copper (Cu), iron (Fe), strontium (Sr), tungsten (W), vanadium (V), chromium (Cr), tin (Sn), hafnium (Hf), indium (In), cadmium (Cd), molybdenum (Mo), tantalum (Ta), niobium (Nb), aluminum (Al), cesium (Cs), barium (Ba), lanthanum (La), cerium (Ce), silver (Ag), antimony (Sb), combinations thereof, or oxides thereof. In some embodiments, the metal particles comprise one or more selected from the group consisting of Ce, Ba, La, In, Sn, Ag, Sb, and oxides thereof.
[0094] In some embodiments, the metal nanoparticles have an average particle size of about 2 nm to about 5 nm. In some embodiments, the amount of metal nanoparticles in the resist composition is in the range of about 0.5 wt% to about 15 wt% based on the weight of the nanoparticles and the solvent. In some embodiments, the amount of nanoparticles in the resist composition is in the range of about 5 wt% to about 10 wt% based on the weight of the nanoparticles and the solvent. In some embodiments, the concentration of metal particles is in the range of 1 wt% to 7 wt% based on the weight of the solvent and the metal particles. If the metal nanoparticles are less than about 0.5 wt%, the resist coating is too thin. If the metal nanoparticles are more than about 15 wt%, the resist coating is too thick and viscous.
[0095] In some embodiments, the metallic core is complexed by a ligand, wherein the ligand comprises a branched or unbranched, cyclic or acyclic, saturated organic group comprising a C1-C7 alkyl group or a C1-C7 fluoroalkyl group. The C1-C7 alkyl group or C1-C7 fluoroalkyl group comprises one or more substituents selected from the group consisting of -CF3, -SH, -OH, =O, -S-, -P-, -PO2, -C(=O)SH, -C(=O)OH, -C(=O)O-, -O-, -N-, -C(=O)NH, -SO2OH, -SO2SH, -SOH, and -SO2-. In some embodiments, the ligand comprises one or more substituents selected from the group consisting of -CF3, -OH, -SH, and -C(=O)OH substituents.
[0096] In some embodiments, the ligand is a carboxylic acid or sulfonic acid ligand. For example, in some embodiments, the ligand is methacrylic acid. In some embodiments, the metal particle is a nanoparticle, and the metal nanoparticle is complexed with a ligand comprising an aliphatic or aromatic group. The aliphatic or aromatic group may be unbranched or branched into a cyclic or acyclic saturated pendant group containing 1 to 9 carbons, including an alkyl group, an alkenyl group, and a phenyl group. The branched group may be further substituted with oxygen or a halogen. In some embodiments, each metal particle is complexed by 1 to 25 ligand units. In some embodiments, each metal particle is complexed by 3 to 18 ligand units.
[0097] In some embodiments, the resist composition comprises about 0.1 wt% to about 20 wt% of ligands based on the total weight of the resist composition. In some embodiments, the resist comprises about 1 wt% to about 10 wt% of ligands. In some embodiments, the ligand concentration is about 10 wt% to about 40 wt% based on the weight of the metal particles and the weight of the ligands. If the ligand is less than about 10 wt%, the organometallic photoresist does not function well. If the ligand is more than about 40 wt%, it is difficult to form a consistent photoresist layer. In some embodiments, the ligand(s) are dissolved in a coating solvent, for example, propylene glycol methyl ether acetate (PGMEA), in a range of about 5 wt% to about 10 wt% based on the weight of the ligand(s) and the solvent.
[0098] In some embodiments, the copolymer and PAC are added to a solvent for application along with any desired additive or other formulation. After addition, the mixture is mixed to achieve a uniform composition throughout the photoresist to ensure that there are no defects caused by uneven mixing or non-uniform composition of the photoresist. Once mixed, the photoresist can be stored until use or used immediately.
[0099] The solvent may be any suitable solvent including the solvent used to coat the lower layer composition as described herein.
[0100] Some embodiments of the photoresist include one or more photoactive compounds (PACs). The PAC is a photoactive component, for example, a photo-generating agent (PAG), a photobase (PBG) generator, a photodegradable base (PDB), a free radical generator, etc. The PAC may be positively functional or negatively functional. In some embodiments where the PAC is a photogenerator (PAG), the PAC comprises halogenated triazines, onium salts, diazonium salts, aromatic diazonium salts, phosphonium salts, sulfonium salts, iodonium salts, oxime sulfonates, diazodisulfones, disulfones, o-nitrobenzylsulfonates, sulfonated esters, halogenated sulfonyloxy dicarboxymides, α-cyanooxyamine-sulfonates, imidosulfonates, ketodiazosulfones, sulfonyl diazoesters, 1,2-di(arylsulfonyl)hydrazines, nitrobenzyl esters, and s-triazine derivatives, combinations thereof, etc.
[0101] Specific examples of PAGs include α-(trifluoromethylsulfonyloxy)-bicyclo[2.2.1]hept-5-en-2,3-dicarboxymide (MDT), N-hydroxy-naphthalimide (DDSN), benzoin tosylate, t-butylphenyl-α-(p-toluenesulfonyloxy)-acetate and t-butyl-α-(p-toluenesulfonyloxy)-acetate, triarylsulfonium and diaryl iodonum hexafluoroantimonate, hexafluoroarsenate, trifluoromethanesulfonate, iodonum perfluorooctanesulfonate, N-camporsulfonyloxynaphthalimide, N-pentafluorophenylsulfonyloxynaphthalimide, ionic iodonum sulfonates, e.g., diaryl iodonum (alkyl or aryl)sulfonate and Bis-(di-t-butylphenyl)iodonium campanylsulfonate, perfluoroalkansulfonate, e.g., perfluoropentanesulfonate, perfluorooctanesulfonate, perfluoromethanesulfonate, aryl (e.g., phenyl or benzyl)triplate, e.g., triphenylsulfonium trilate or bis-(t-butylphenyl)iodonium trilate; pyrogallol derivatives (e.g., trimesylate of pyrogallol), trifluoromethanesulfonate esters of hydroxyimide, α,α'-bis-sulfonyl-diazomethane, sulfonate esters of nitro-substituted benzyl alcohol, naphthoquinone-4-diazide, alkyl disulfone, etc.
[0102] In some embodiments, the PAG in the photosensitive layer (120) contains an anion or cation different from the anion or cation of the photogenerator bonded to the polymer in the intermediate layer (115).
[0103] In some embodiments where the PAC is a free radical generator, the PAC comprises n-phenylglycine; aromatic ketones including benzophenone, N,N'-tetramethyl-4,4'-diaminobenzophenone, N,N'-tetraethyl-4,4'-diaminobenzophenone, 4-methoxy-4'-dimethylaminobenzophenone, 3,3'-dimethyl-4-methoxybenzophenone, p,p'-bis(dimethylamino)benzophenone, and p,p'-bis(diethylamino)-benzophenone; anthraquinone, 2-ethylanthraquinone; naphthaquinone; and phenanthraquinone; benzoin including benzoin, benzoin methyl ether, benzoin isopropyl ether, benzoin-n-butyl ether, benzoin-phenyl ether, methylbenzoin, and ethylbenzoin; Benzyl derivatives including dibenzyl, benzyl diphenyl disulfide, and benzyl dimethyl ketal; acridine derivatives including 9-phenylacridine and 1,7-bis(9-acridinyl)heptane; thioxantones including 2-chlorothioxantone, 2-methylthioxantone, 2,4-diethylthioxantone, 2,4-dimethylthioxantone, and 2-isopropylthioxantone; acetophenones including 1,1-dichloroacetophenone, pt-butyldichloro-acetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, and 2,2-dichloro-4-phenoxyacetophenone; 2,4,5-triarylimidazole dimers including 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di-(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer, 2,4-di(p-methoxyphenyl)-5-phenylimidazole dimer, 2-(2,4-dimethoxyphenyl)-4,5-diphenylimidazole dimer and 2-(p-methylmercaptophenyl)-4,5-diphenylimidazole dimer; combinations thereof, etc.
[0104] As will be recognized by those skilled in the art, the chemical compounds listed herein are intended only as exemplified examples of PACs and are not intended to limit the embodiments to these specifically described PACs. Rather, any suitable PAC may be used, and all such PACs are fully intended to be included within the scope of the embodiments of the present invention.
[0105] In some embodiments, a crosslinking agent or coupling agent is added to the photoresist. Additionally, to crosslink and bond two hydrocarbon structures together, the crosslinking agent reacts with one group from one of the hydrocarbon structures in the polymer resin and reacts with a second group from a distinct one of the hydrocarbon structures. This bonding and crosslinking increases the molecular weight of the polymer product of the crosslinking reaction and increases the overall linking density of the photoresist. The density and linking density help improve the resist pattern. The coupling agent assists the crosslinking reaction. The crosslinking agent or coupling agent may be any crosslinking agent or coupling agent disclosed herein with reference to the lower section.
[0106] The individual components of the photoresist are placed in a solvent to assist in the mixing and dispersion of the photoresist. To assist in the mixing and dispersion of the photoresist, the solvent is selected at least partially based on the material selected for the polymer resin as well as the PAC. In some embodiments, the solvent is selected so that the polymer resin and the PAC can be evenly dissolved in the solvent and dispersed over the layer to be patterned.
[0107] In some embodiments, a quencher is added to the photoresist to inhibit the diffusion of acid / base / free radicals generated within the photoresist. The quencher improves the stability of the photoresist over time as well as the resist pattern configuration. In some embodiments, the quencher is a photodegradable quencher (PDQ). In some embodiments, the PDQ is selected from the group consisting of 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidium n-butyltriphenylborate, 2-nitrophenylmethyl 4-methacryloyloxypiperidine-1-carboxylate, quaternary ammonium dithiocarbamate, α-aminoketone, oxime-urethane, dibenzophenone oxime hexamethylene diurethane, ammonium tetraorganylborate salt, and N-(2-nitrobenzyloxycarbonyl)cyclic amine, and combinations thereof. In some embodiments, PDQ is identical to a photobase generator (PBG).
[0108] In some embodiments, another additive added to the photoresist is a stabilizer that helps prevent the unwanted diffusion of acid generated during the exposure of the photoresist.
[0109] In some embodiments, another additive added to the photoresist is a dissolution inhibitor that helps control the dissolution of the photoresist during development.
[0110] Colorants are another additive added to the photoresist in some embodiments. A colorant observer tests the photoresist and identifies any defects that may need to be improved before further processing.
[0111] In some embodiments, a surface leveling agent is added to assist in making the upper surface of the photoresist uniform, so that impact light will not be negatively altered by the uneven surface.
[0112] When prepared, the photoresist material is applied over the intermediate layer (115) as shown in FIG. 4 to form a photoresist layer (120). In some embodiments, the photoresist is applied using a process such as a spin-on coating process, a dip coating method, an air-knife coating method, a curtain coating method, a wire-bar coating method, a gravure coating method, a stacking method, an extrusion coating method, or a combination thereof. In some embodiments, the thickness of the photoresist layer (120) is in the range of about 10 nm to about 300 nm.
[0113] In some embodiments, the developer (57) is applied to the photoresist layer (120) using a spin-on process during the development operation (S145). In the spin-on process, as illustrated in FIG. 6, while the photoresist-coated substrate is rotating, the developer (57) is applied to the photoresist layer (120) from above. In some embodiments, while the photoresist-coated substrate (10) is rotated at a speed of about 100 rpm to about 2000 rpm, the developer (57) is applied at a speed of about 5 ml / min to about 800 ml / min. In some embodiments, the developer is at a temperature of about 10°C to about 80°C. In some embodiments, the development operation continues for about 30 seconds to about 10 minutes.
[0114] While a spin-on process is one suitable method for developing the photoresist layer (120) after exposure, this is intended for illustrative purposes only and not to limit the embodiments. Rather, any suitable development process, including a dip process, a puddle process, and a spray-on method, may be used alternatively. All such development processes are included within the scope of the embodiments.
[0115] In some embodiments, the photoresist developer (57) comprises a solvent and an acid or a base. In some embodiments, the concentration of the solvent is about 60% by weight to about 99% by weight based on the total weight of the photoresist developer. The concentration of the acid or base is about 0.001% by weight to about 20% by weight based on the total weight of the photoresist developer. In a specific embodiment, the concentration of the acid or base in the developer is about 0.01% by weight to about 15% by weight based on the total weight of the photoresist developer.
[0116] In some embodiments, the developer is an aqueous solution, for example, an aqueous solution of tetramethylammonium hydroxide. In other embodiments, the developer (57) is an organic solvent. The organic solvent may be any suitable solvent. In some embodiments, the solvent is one or more solvents selected from propylene glycol methyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), 1-ethoxy-2-propanol (PGEE), γ-butyrolactone (GBL), cyclohexanone (CHN), ethyl lactate (EL), methanol, ethanol, propanol, n-butanol, 4-methyl-2-pentanol, acetone, methyl ethyl ketone, dimethylformamide (DMF), isopropanol (IPA), tetrahydrofuran (THF), methyl isobutyl carbinol (MIBC), n-butyl acetate (nBA), 2-heptanone (MAK), and dioxane.
[0117] In some embodiments, the three-layer resist of the present disclosure is used in the manufacture of semiconductor devices, for example, in the gate structure of a field-effect transistor (FET). Embodiments such as those disclosed herein may generally be applied to planar FETs as well as FinFETs, double-gate FETs, surround-gate FETs, omega-gate FETs or gate-all-around (GAA) FETs, and / or nanowire transistors, or any suitable device having one or more work function modulation (WFM) layers in the gate structure.
[0118] In FET structures forming multiple devices with different threshold voltages (Vt), the composition and dimensions of the metal gate layer play a significant role in defining Vt. Multiple FETs with different threshold voltages can be realized by controlling the material and / or dimensions of one or more work function control materials (WFM) placed between the gate dielectric layer and the body metal gate electrode layer (e.g., W layer). If there is insufficient control of the photolithographic operation, the dimensions of the metal gate layer may be inconsistent, which affects its work function, thereby affecting the threshold voltage and degrading device performance.
[0119] In the following embodiments, a method for providing a WFM layer with consistent and controlled dimensions is discussed.
[0120] FIG. 29 shows a cross-sectional view of a gate structure for FETs having different threshold voltages according to an embodiment of the present disclosure. In some embodiments, the semiconductor device comprises a first n-type FET (N1), a second n-type FET (N2), a third n-type FET (N3), a first p-type FET (P1), a second p-type FET (P2), and a third p-type FET (P3). The threshold voltage of the first n-type FET (N1) has an absolute value smaller than the threshold voltage of the second n-type FET (N2), and the threshold voltage of the second n-type FET (N2) has an absolute value smaller than the threshold voltage of the third n-type FET (N3). Similarly, the threshold voltage of the first p-type FET (P1) has an absolute value smaller than the threshold voltage of the second p-type FET (P2), and the threshold voltage of the second p-type FET (P2) has an absolute value smaller than the threshold voltage of the third p-type FET (P3).
[0121] FIGS. 30a-30r shows cross-sectional views of various steps of manufacturing a semiconductor device illustrated in FIG. 29 according to embodiments of the present disclosure. In a sequential manufacturing process, one or more additional operations may be provided before, during, and after the steps illustrated in FIGS. 30a-30r, and it is understood that some of the operations described below may be replaced or removed for further embodiments of the method. The order of operations / processes may be interchanged. Accordingly, one or more operations illustrated in FIGS. 30a-30r may be omitted or replaced with another operation depending on the structure of the semiconductor device.
[0122] FIG. 30a illustrates a plurality of channel regions of a first n-type FET (N1), a second n-type FET (N2), a third n-type FET (N3), a first p-type FET (P1), a second p-type FET (P2), and a third p-type FET (P3), respectively. An interface layer (210) is formed over each channel region. A gate dielectric layer (e.g., a high-k gate dielectric layer) (230) is formed over each interface layer (210). A first conductive layer is formed over each gate dielectric layer (230) as a cap layer (235).
[0123] In some embodiments, the interface layer (210) is formed using chemical oxidation. In some embodiments, the interface layer (210) comprises one of silicon oxide, silicon nitride, and a mixed silicon-germanium oxide. In some embodiments, the thickness of the interface layer (210) is in the range of about 0.2 nm to about 6 nm. In some embodiments, the gate dielectric layer (230) comprises one or more layers of a dielectric material, for example, silicon oxide, silicon nitride, or a high dielectric constant dielectric material, other suitable dielectric materials, and / or combinations thereof. Examples of high dielectric constant dielectric materials include HfO2, HfSiO, HfSiON, HfTaO, HfTiO, HfZrO, zirconium oxide, aluminum oxide, titanium oxide, hafnium dioxide-alumina (HfO2-Al2O3) alloy, La2O3, HfO2-La2O3, Y2O3, or other suitable high dielectric constant dielectric materials, and / or combinations thereof. The gate dielectric layer (230) may be formed by CVD, ALD, or any suitable method. In one embodiment, the gate dielectric layer (230) is formed using a highly conformal deposition process, such as ALD, to ensure the formation of a gate dielectric layer with a single thickness around each channel layer. In some embodiments, the thickness of the gate dielectric layer (230) is in the range of about 1 nm to about 100 nm. In some embodiments, the first conductive layer (235) is a TiN or TiSiN layer formed by CVD, ALD, or any suitable method.
[0124] In some embodiments, the second conductive layer is formed on the cap layer (235) as the first barrier layer (245) as shown in FIG. 30b. In some embodiments, the cap layer (235) is removed after an annealing operation, and the first barrier layer (245) is not formed. In some embodiments, the second conductive layer (245) comprises metal nitrides, for example, WN, TaN, TiN, and TiSiN. In some embodiments, TaN is used. The thickness of the second conductive layer (245) is in the range of about 0.3 nm to about 30 nm in some embodiments and in the range of about 0.5 nm to about 25 nm in other embodiments. In some embodiments, the second conductive layer (245) functions as a barrier layer or an etching stop layer. In some embodiments, the second conductive layer (245) is thinner than the first conductive layer (235).
[0125] As illustrated in FIG. 30c, in some embodiments, a WFM layer (200) is formed. In some embodiments, the WFM layer (200) is an n-type WFM layer. In some embodiments, the WFM layer is made of a single layer of a conductive material, for example, TiN, WN, TaAlC, TiC, TaAl, TaC, Co, Al, TiAl, or TiAlC, or a multilayer of two or more of these materials. In some embodiments, for an n-type FET, an aluminum-containing layer, for example, TiAl, TiAlC, TaAl and / or TaAlC, is used as the n-type WFM layer (200), and for a p-type FET, one or more of TaN, TiN, WN, TiC, WCN, MoN and / or Co are used as the p-type WFM layer. In some embodiments, the n-type WFM layer comprises a material having a low work function in the range of 2.5 eV to about 4.4 eV or having low electronegativity. In some embodiments, the p-type WFM layer comprises a material having a high work function in the range of about 4.3 eV to 5.8 eV and / or high electronegativity. In some embodiments, the thickness of the n-type WFM layer (200) is in the range of about 0.6 nm to about 40 nm, and in other embodiments, is in the range of about 1 nm to about 20 nm.
[0126] A first patterning operation is performed to remove the n-type WFM layer (200) from the regions for the first p-type FET (P1), the second p-type FET (P2), and the third p-type FET (P3). In some embodiments, a lower layer (260) made of the lower layer composition disclosed herein with reference to FIGS. 15-18c is formed on each n-type WFM layer (200). An intermediate layer (300) (e.g., FIGS. 3 and 19-28) made according to embodiments disclosed herein is formed on each lower layer (260), and a photoresist layer (205) made of any photoresist composition disclosed herein is formed on each intermediate layer (300) as shown in FIG. 30d. Using one or more lithography operations, the photoresist layer (205) is patterned to expose the intermediate layer (300) in the region for the p-type FET. Next, as illustrated in FIG. 30e, the exposed intermediate layer (300) and lower layer (260) are removed by one or more etching operations to expose an n-type WFM layer (200) in the area for the p-type FET. In some embodiments, the plasma etching operation uses a gas containing N2 and H2, a gas containing O2 / Cl2, or an O2 gas.
[0127] Subsequently, as illustrated in FIG. 30f, the n-type WFM layer (200) in the region for the p-type FET is removed by an appropriate etching operation. In some embodiments, the etching operation includes a wet etching operation. In some embodiments, the etching solution (etching liquid) comprises an aqueous solution of HCl and H2O2, an aqueous solution of a combination of NH4OH and H2O2, an aqueous solution of a combination of HCl, NH4OH and H2O2, an aqueous solution of HF, NH4OH and H2O2, and / or an aqueous solution of H3PO4 and H2O2. The wet etching is substantially interrupted at the first barrier layer (245), and thus functions as an etching stop layer. In some embodiments, the gate dielectric layer (230) acts as an etching stop layer instead of the first barrier layer.
[0128] After the wet etching operation, in some embodiments, a wet cleaning operation or a deionized water rinse is performed. As illustrated in FIG. 30g, the photoresist layer (205), the intermediate layer (300), and the lower layer (260) are subsequently removed from the n-type FET region. In some embodiments, a plasma ashing operation using an oxygen-containing gas is performed to remove the organic photoresist layer (205), the intermediate layer, and the lower layer (260). In some embodiments, an N2 / H2-based plasma or a CF4-based plasma is used for the plasma ashing operation.
[0129] In some embodiments, as illustrated in FIG. 30h, a third conductive layer as a second barrier layer (250) is formed on an n-type WFM layer (200) for an n-type FET and on a first barrier layer (245) in a region for a p-type FET. In some embodiments, a blanket layer of the second barrier layer (250) is formed on regions of the n-type and p-type FETs. In some embodiments, TaN is used as the third conductive layer (250). The thickness of the third conductive layer (250) is in the range of about 0.3 nm to about 30 nm in some embodiments and in the range of about 0.5 nm to about 25 nm in other embodiments.
[0130] As illustrated in FIG. 30i, the blanket layer of the first p-type WFM layer (280) is formed on each second barrier layer (250) in the regions for the n-type and p-type FETs. In some embodiments, the thickness of the first p-type WFM layer (280) is in the range of about 0.5 nm to about 20 nm, and in other embodiments, it is in the range of about 1 nm to about 10 nm.
[0131] Next, a second patterning operation is performed to remove the first p-type WFM layer (280) from the region for the first and second n-type FETs (N1, N2) and the second and third p-type FETs (P2, P3). A second lower layer (265) made of the lower layer composition disclosed herein is formed on each of the first p-type WFM layers (280). As illustrated in FIG. 30j, a second intermediate layer (305) made of the intermediate layer composition disclosed herein is formed on each of the second lower layers, and a second photoresist layer (215) formed of any photoresist composition disclosed herein is formed on the second intermediate layer (305). Using one or more lithography operations, the second photoresist layer (215) is patterned and the second intermediate layer (305) is exposed to light in the region for the first and second n-type FETs (N1, N2) and the second and third p-type FETs (P2, P3). Next, as illustrated in FIG. 30k, the exposed intermediate layer (305) and the second lower layer (265) are removed by one or more plasma etching operations to expose the first p-type WFM layer (280) in the area for the first and second n-type FETs (N1, N2) and the second and third p-type FETs (P2, P3). Plasma etching uses a gas containing N2 and H2, a gas containing O2 / Cl2, or an O2 gas.
[0132] Subsequently, as illustrated in FIG. 30, the first p-type WFM layer (280) in the region for the first and second n-type FETs (N1, N2) and the second and third p-type FETs (P2, P3) is removed by a suitable etching operation. In some embodiments, the etching operation includes a wet etching operation. In some embodiments, the etching solution (etching liquid) includes an aqueous solution of H3PO4 and H2O2, or an aqueous solution of a combination of HCl, NH4OH, and H2O2. The wet etching is substantially interrupted at the second barrier layer (250), and thus functions as an etching stop layer.
[0133] After the wet etching operation, in some embodiments, a wet cleaning operation or a deionized water rinse is performed. As illustrated in FIG. 30m, the second photoresist layer (215), the second intermediate layer (305), and the second lower layer (265) are subsequently removed. In some embodiments, a plasma ashing operation using an oxygen-containing gas is performed to remove the organic second photoresist layer (215), the second intermediate layer, and the second lower layer (265). In some embodiments, an N2 / H2-based plasma or a CF4-based plasma is used for the plasma ashing operation.
[0134] As illustrated in FIG. 30n, the blanket layer of the second p-type WFM layer (285) is formed on the second barrier layer (250) in the region for the first and second n-type FETs (N1, N2) and the second and third p-type FETs (P2, P3), and in some embodiments, is formed on the first p-type WFM layer (280) in the region for the third n-type FET (N3) and the first p-type FET (P1). In some embodiments, the thickness of the second p-type WFM layer (285) is in the range of about 0.5 nm to about 20 nm, and in other embodiments, is in the range of about 1 nm to about 10 nm.
[0135] A third patterning operation is performed substantially to remove the second p-type WFM layer (285) from the region for the first n-type FET (N1) and the third p-type FET (P3). In some embodiments, as shown in FIG. 30o, a third lower layer (270) made of the lower layer composition disclosed herein is formed over the second p-type WFM layer (285), a third intermediate layer (310) made of any intermediate layer composition disclosed herein, and a third photoresist layer (225) made of any photoresist composition disclosed herein are formed over the third lower layer (270). Using one or more lithography operations, the third photoresist layer (225) is patterned so that the third intermediate layer (310) is exposed to the region for the first n-type FET (N1) and the third p-type FET (P3). Next, as illustrated in FIG. 30p, the exposed third intermediate layer (310) and third lower layer (270) are removed by one or more plasma etching operations to expose the second p-type WFM layer (285) in the area for the first n-type FET (N1) and the third p-type FET (P3). Plasma etching uses a gas containing N2 and H2, a gas containing O2 / Cl2, or an O2 gas.
[0136] Subsequently, as illustrated in FIG. 30q, the second p-type WFM layer (285) in the region for the first n-type FET (N1) and the third p-type FET (P3) is removed by an appropriate etching operation. In some embodiments, the etching operation includes a wet etching operation. In some embodiments, the etching solution (etching liquid) includes an aqueous solution of H3PO4 and H2O2, or an aqueous solution of a combination of HCl, NH4OH, and H2O2. The wet etching is substantially stopped at the second barrier layer (250), and thus functions as an etching stop layer.
[0137] After the wet etching operation, in some embodiments, a wet cleaning operation or a deionized water rinse is performed. As illustrated in FIG. 30r, the third photoresist layer (225), the third intermediate layer (310), and the third lower layer (270) are subsequently removed. In some embodiments, a plasma ashing operation using an oxygen-containing gas is performed to remove the third photoresist layer (225), the third intermediate layer (310), and the lower layer (270). In some embodiments, an N2 / H2-based plasma or a CF4-based plasma is used for the plasma ashing operation.
[0138] A glue layer (290) is subsequently formed on a second barrier layer (250) in a region for a first n-type FET (N1) and a third p-type FET (P3), and formed on a second p-type WFM layer (285) in a region for a second and third n-type FET (N2, N3) and a first and second p-type FET (P1, P2), and in some embodiments, a body gate electrode layer (295) is formed on the glue layer (290) to provide a semiconductor device illustrated in FIG. 29.
[0139] In some embodiments, the glue layer (290) is made of TiN, Ti, or Co. In some embodiments, the body gate electrode layer (295) comprises one or more layers of a conductive material, for example, polysilicon, aluminum, copper, titanium, tantalum, tungsten, cobalt, molybdenum, tantalum nitride, nickel silicide, cobalt silicide, TiN, WN, TiAl, TiAlN, TaCN, TaC, TaSiN, metallic metal, other suitable materials, and / or combinations thereof.
[0140] Other embodiments include other operations before, during, or after the operations described above. In some embodiments, the disclosed method includes the step of forming a semiconductor device comprising a fin field-effect transistor (FinFET) structure. In some embodiments, a plurality of active fins are formed on a semiconductor substrate. Such embodiments further include the step of etching the substrate through an opening in a patterned hard mask to form trenches in the substrate; the step of filling the trenches with a dielectric material; the step of performing a chemical mechanical polishing (CMP) process to form shallow trench isolation (STI) features; and the step of epitaxially growing or resetting the STI features to form fin-shaped active regions. In some embodiments, one or more gate electrodes are formed on the substrate. Some embodiments include the step of forming gate spacers, doped source / drain regions, contacts for gate / source / drain features, etc. In other embodiments, the target pattern is formed as metal lines of a multilayer wiring structure. For example, the metal lines may be formed in an interlayer dielectric (ILD) layer of the substrate, which is etched to form a plurality of trenches. The trenches may be filled with a conductive material, for example, a metal; the conductive material may be polished using a process such as chemical mechanical planarization (CMP) to expose a patterned ILD layer, thereby forming metal lines on the ILD layer. The above is a non-limiting example of an apparatus / structure that may be made or / or improved using the method described herein.
[0141] In some embodiments, depending on the embodiment of the disclosure, active components, e.g., diodes, field effect transistors (FETs), metal oxide semiconductor field effect transistors (MOSFETs), complementary metal oxide semiconductor (CMOS) transistors, bipolar transistors, high-voltage transistors, high-frequency transistors, FinFETs, other three-dimensional (3D) FETs, other memory cells, and combinations thereof are formed.
[0142] The novel intermediate layer composition and method for manufacturing a semiconductor device according to the present disclosure provide a higher semiconductor device feature yield. Embodiments of the present disclosure include a method and a material that reduce scum defects, thereby improving pattern resolution, reducing line width roughness, reducing line edge roughness, and improving semiconductor device yield. Embodiments of the disclosure further enable effective exposure and patterning of a photoresist using a low exposure dose.
[0143] An embodiment of the disclosure is a method for manufacturing a semiconductor device comprising the step of forming a first layer comprising an organic material on a substrate. A second layer is formed on the first layer, wherein the second layer comprises one or more selected from the group consisting of a photogenerator, a chemical radiation absorbing additive comprising an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material. A photosensitive layer is formed on the second layer, and the photosensitive layer is patterned. In an embodiment, the silicon-containing material is a siloxane or spin-on glass. In an embodiment, the second layer comprises a photogenerator, and the photogenerator comprises a sulfonium or iodonium cation. In an embodiment, the second layer comprises a photogenerator, and the photogenerator is bonded to a silicon-containing material. In an embodiment, the formation of the second layer comprises applying a mixture to the first layer, wherein the mixture comprises one or more of a photogenerator, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material; The mixture is applied over a first layer and then heated at a temperature in the range of 40°C to 400°C. In an embodiment, the second layer comprises a silicon-containing monomer having an iodine or phenolic group substituent, and the formation of the second layer comprises applying a mixture comprising a silicon-containing material and a silicon-containing monomer over a first layer, and then crosslinking the mixture by heating the mixture to a temperature in the range of 150°C to 400°C after applying the mixture over the first layer. In an embodiment, the application of the mixture comprises spin coating of the mixture, and during spin coating, the silicon-containing monomer is at least partially separated from the mixture to form an upper second layer and a lower second layer, wherein the upper second layer has a higher concentration of silicon-containing monomer than the lower second layer. In an embodiment, during crosslinking of the mixture, the silicon-containing monomer in the upper second layer is crosslinked.
[0144] Another embodiment of the disclosure is a method for manufacturing a semiconductor device comprising the step of forming a lower anti-reflective coating layer on a substrate. An intermediate layer is formed on the lower anti-reflective coating layer, wherein the intermediate layer comprises one or more selected from the group consisting of a photogenerator, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material. A photosensitive layer is formed on the intermediate layer. The photosensitive layer is selectively exposed to chemical radiation to form a latent image pattern, and the selectively exposed photosensitive layer is developed to form a pattern in the photosensitive layer. In an embodiment, the silicon-containing material is a polysiloxane. In an embodiment, the intermediate layer comprises a photogenerator, and the photogenerator comprises a sulfonium cation or an iodonium cation. In an embodiment, the intermediate layer comprises a photogenerator, and the photogenerator
[0145]
[0146] An anion selected from the group consisting of, and
[0147]
[0148] It includes a cation selected from the group consisting of
[0149] In an embodiment, the intermediate layer comprises a chemical radiation absorbing additive having an iodine substituent, and the additive is structure I n -R1, where n = 1-10, and R1 is selected from the group consisting of substituted or unsubstituted C1-C10 alkyl groups, C6-C10 aryl groups, C1-C10 aralkyl groups, C3-C10 cycloalkyl groups, C1-C10 hydroxyalkyl groups, C2-C10 alkoxyalkyl groups, C2-C10 acetyl groups, C3-10 acetylalkyl groups, C1-C10 carboxyl groups, C2-C10 alkyl carboxyl groups, C3-C10 cycloalkyl carboxyl groups, or adamantyl groups. In an embodiment, the intermediate layer comprises a chemical radiation absorbing additive having an iodine substituent, and the additive
[0150]
[0151] It is selected from a group consisting of.
[0152] In an embodiment, the intermediate layer comprises a silicon-containing monomer having an iodine or phenol group substituent, wherein the silicon-containing monomer has the following structure:
[0153]
[0154] In the above formula, Z and D are independently substituted or unsubstituted C1-C20 alkyl groups, C3-C20 cycloalkyl groups, C1-C20 hydroxyalkyl groups, C2-C20 alkoxy groups, C3-C20 alkoxyalkyl groups, C2-C20 acetyl groups, C3-C20 acetyl alkyl groups, C1-C20 carboxyl groups, C2-C20 alkyl carboxyl groups, C1-C20 alkyl fluoride groups, C6-C20 aryl groups, C7-C20 aralkyl groups, or adamantyl groups, wherein Z and D independently comprise 1-10 iodine or 1-10 phenolic OH groups, Z is a single bond, and D is H; R4, R5, and R6 are each H or a substituted or unsubstituted C6-C20 aryl group, C7-C20 aralkyl group, C3-C20 cycloalkyl group, C1-C20 hydroxyalkyl group, C2-C20 alkoxy group, C3-C20 alkoxyalkyl group, C2-C20 acetyl group, C3-C20 acetylalkyl group, C1-C20 carboxyl group, C2-C20 alkyl carboxyl group, or C4-C20 cycloalkyl carboxyl group. In an embodiment, the intermediate layer comprises a silicon-containing monomer having an iodine or phenol group substituent, wherein the silicon-containing monomer is
[0155]
[0156]
[0157]
[0158] It is selected from a group consisting of.
[0159] In an embodiment, the intermediate layer comprises a silicon-containing monomer having an iodine or phenol group substituent, and the silicon-containing monomer comprises a photogenerator substituent, and
[0160]
[0161] It is selected from a group consisting of.
[0162] Another embodiment of the disclosure is a method for manufacturing a semiconductor device comprising the step of forming a lower layer of a three-layer resist on a substrate. An intermediate layer of the three-layer resist is formed on the lower layer. The intermediate layer comprises one or more selected from the group consisting of a photogenerative agent, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material. The intermediate layer is heated at a temperature in the range of 40°C to 400°C. A photosensitive layer is formed on the intermediate layer after heating the intermediate layer. The photosensitive layer and the intermediate layer are optionally exposed to chemical radiation. A developer composition is applied to the optionally exposed photosensitive layer to form a pattern on the photosensitive layer. In an embodiment, the silicon-containing material is polysiloxane or spin-on glass. In an embodiment, the chemical radiation is extreme ultraviolet radiation.
[0163] Another embodiment of the disclosure is a composition comprising one or more selected from the group consisting of a photogenerator, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material. The photogenerator
[0164]
[0165] An anion selected from the group consisting of, and
[0166]
[0167] It includes a cation selected from the group consisting of
[0168] Chemical radiation absorbing additives having iodine substituents are structure I n -R1, where n = 1-10, and R1 is selected from the group consisting of substituted or unsubstituted C1-C10 alkyl groups, C6-C10 aryl groups, C1-C10 aralkyl groups, C3-C10 cycloalkyl groups, C1-C10 hydroxyalkyl groups, C2-C10 alkoxyalkyl groups, C2-C10 acetyl groups, C3-10 acetylalkyl groups, C1-C10 carboxyl groups, C2-C10 alkyl carboxyl groups, C3-C10 cycloalkyl carboxyl groups, or adamantyl groups. The silicon-containing monomer has the following structure:
[0169]
[0170] In the above formula, Z and D are substituted or unsubstituted C1-C20 alkyl groups, C3-C20 cycloalkyl groups, C1-C20 hydroxyalkyl groups, C2-C20 alkoxy groups, C3-C20 alkoxyalkyl groups, C2-C20 acetyl groups, C3-C20 acetyl alkyl groups, C1-C20 carboxyl groups, C2-C20 alkyl carboxyl groups, C1-C20 alkyl fluoride groups, C6-C20 aryl groups, C7-C20 aralkyl groups, or adamantyl groups, wherein Z and D independently comprise 1-10 iodine or 1-10 phenolic OH groups, Z is a single bond, and D is H; R4, R5, and R6 are each H or a substituted or unsubstituted C6-C20 aryl group, C7-C20 aralkyl group, C3-C20 cycloalkyl group, C1-C20 hydroxyalkyl group, C2-C20 alkoxy group, C3-C20 alkoxyalkyl group, C2-C20 acetyl group, C3-C20 acetylalkyl group, C1-C20 carboxyl group, C2-C20 alkyl carboxyl group, or C4-C20 cycloalkyl carboxyl group. In an embodiment, the silicon-containing material is a siloxane or spin-on glass. In an embodiment, the silicon-containing material is a polysiloxane. In an embodiment, the composition comprises a chemical radiation absorbing additive having an iodine substituent, and the additive
[0171]
[0172] It is selected from a group consisting of.
[0173] In an embodiment, the composition comprises a silicon-containing monomer having an iodine or phenol group substituent, wherein the silicon-containing monomer
[0174]
[0175]
[0176] It is selected from a group consisting of.
[0177] In an embodiment, the composition comprises a solvent. In an embodiment, the composition comprises a silicon-containing monomer, and the silicon-containing monomer has a lower density than the silicon-containing material and the solvent. In an embodiment, a photogenerator is bonded to the silicon-containing material.
[0178] Another embodiment of the disclosure is a composition comprising a photogenerator comprising an anion and a cation, and a silicon-containing material. The anion comprises one or more iodines. In an embodiment, the anion is
[0179]
[0180] It is one or more anions selected from the group consisting of
[0181] In an embodiment, the cation is
[0182]
[0183] It is one or more cations selected from the group consisting of
[0184] In an embodiment, the composition comprises a chemical radiation-absorbing additive having an iodine substituent. In an embodiment, the radiation-absorbing additive has structure I n-R1, where n = 1-10, and R1 is selected from the group consisting of substituted or unsubstituted C1-C10 alkyl groups, C6-C10 aryl groups, C1-C10 aralkyl groups, C3-C10 cycloalkyl groups, C1-C10 hydroxyalkyl groups, C2-C10 alkoxyalkyl groups, C2-C10 acetyl groups, C3-10 acetylalkyl groups, C1-C10 carboxyl groups, C2-C10 alkyl carboxyl groups, C3-C10 cycloalkyl carboxyl groups, or adamantyl groups. In an embodiment, the radiation absorbing additive is
[0185]
[0186] It is selected from a group consisting of.
[0187] In an embodiment, the composition comprises a silicon-containing monomer having an iodine or phenol group substituent.
[0188] Another embodiment of the disclosure is a composition comprising a silicon-containing material; and a silicon-containing monomer having the following structure:
[0189]
[0190] In the above formula, Z and D are independently substituted or unsubstituted C1-C20 alkyl groups, C3-C20 cycloalkyl groups, C1-C20 hydroxyalkyl groups, C2-C20 alkoxy groups, C3-C20 alkoxyalkyl groups, C2-C20 acetyl groups, C3-C20 acetyl alkyl groups, C1-C20 carboxyl groups, C2-C20 alkyl carboxyl groups, C1-C20 alkyl fluoride groups, C6-C20 aryl groups, C7-C20 aralkyl groups, or adamantyl groups, wherein Z and D independently comprise 1-10 iodine or 1-10 phenolic OH groups, Z is a single bond, and D is H; R4, R5, and R6 are each H or a substituted or unsubstituted C6-C20 aryl group, C7-C20 aralkyl group, C3-C20 cycloalkyl group, C1-C20 hydroxyalkyl group, C2-C20 alkoxy group, C3-C20 alkoxyalkyl group, C2-C20 acetyl group, C3-C20 acetylalkyl group, C1-C20 carboxyl group, C2-C20 alkyl carboxyl group, or C4-C20 cycloalkyl carboxyl group. In an embodiment, the composition comprises a solvent, and the silicon-containing monomer has a density greater than the density of the silicon-containing material and the density of the solvent. In an embodiment, the silicon-containing monomer
[0191]
[0192] It is one or more selected from a group consisting of
[0193] In an embodiment, the composition comprises a solvent, and the silicon-containing monomer has a density lower than the density of the silicon-containing material and the density of the solvent. In an embodiment, the silicon-containing monomer
[0194]
[0195] It is one or more selected from a group consisting of
[0196] The foregoing describes the features of some embodiments or examples to enable those skilled in the art to better understand aspects of the present disclosure. Those skilled in the art should recognize that the present disclosure can be readily used as a basis for designing or modifying other processes and structures to perform the same purpose and / or achieve some advantages of the embodiments or examples introduced herein. Furthermore, those skilled in the art should recognize that such equivalent components can be made without departing from the spirit and scope of the present disclosure, and that various variations, substitutions, and replacements can be made herein without departing from the spirit and scope of the present disclosure.
Claims
Claim 1 A method for manufacturing a semiconductor device comprising: a step of forming a first layer containing an organic material on a substrate; a step of forming a second layer on the first layer, wherein the second layer comprises one or more selected from the group consisting of a photogenerative agent, an actinic radiation absorbing additive containing an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material; a step of forming a photosensitive layer on the second layer; and a step of patterning the photosensitive layer. Claim 2 A method for manufacturing a semiconductor device according to claim 1, wherein the step of forming a second layer comprises applying a mixture onto a first layer, wherein the mixture comprises one or more of a photocatalytic agent, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material; and after applying the mixture onto the first layer, heating the mixture at a temperature in the range of 40°C to 400°C. Claim 3 A method for manufacturing a semiconductor device according to claim 1, wherein the second layer comprises a silicon-containing monomer having an iodine or phenol group substituent, and the step of forming the second layer comprises: a step of applying a mixture comprising a silicon-containing material and a silicon-containing monomer onto a first layer; and a step of cross-linking the mixture by heating the mixture at a temperature in the range of 150°C to 400°C after applying the mixture onto the first layer. Claim 4 A method for manufacturing a semiconductor device comprising: a step of forming a lower anti-reflective coating layer on a substrate; a step of forming an intermediate layer on the lower anti-reflective coating layer, wherein the intermediate layer comprises one or more selected from the group consisting of a photogenerative agent, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material; a step of forming a photosensitive layer on the intermediate layer; a step of selectively exposing the photosensitive layer to chemical radiation to form a latent image pattern; and a step of developing the selectively exposed photosensitive layer to form a pattern in the photosensitive layer. Claim 5 In paragraph 4, the intermediate layer includes a light-generating agent, and the light-generating agent An anion selected from the group consisting of, and A method for manufacturing a semiconductor device comprising a cation selected from the group consisting of Claim 6 In paragraph 4, the intermediate layer comprises a chemical radiation absorbing additive having an iodine substituent, and the additive A method for manufacturing a semiconductor device selected from a group consisting of Claim 7 A method for manufacturing a semiconductor device according to claim 4, wherein the intermediate layer comprises a silicon-containing monomer having an iodine or phenol group substituent, and the silicon-containing monomer has the following structure: In the above formula, Z and D are independently substituted or unsubstituted C1-C20 alkyl groups, C3-C20 cycloalkyl groups, C1-C20 hydroxyalkyl groups, C2-C20 alkoxy groups, C3-C20 alkoxyalkyl groups, C2-C20 acetyl groups, C3-C20 acetyl alkyl groups, C1-C20 carboxyl groups, C2-C20 alkyl carboxyl groups, C1-C20 alkyl fluoride groups, C6-C20 aryl groups, C7-C20 aralkyl groups, or adamantyl groups, wherein Z and D independently comprise 1-10 iodine or 1-10 phenolic OH groups, Z is a single bond, and D is H; R4, R5, and R6 are each H or a substituted or unsubstituted C6-C20 aryl group, C7-C20 aralkyl group, C3-C20 cycloalkyl group, C1-C20 hydroxyalkyl group, C2-C20 alkoxy group, C3-C20 alkoxyalkyl group, C2-C20 acetyl group, C3-C20 acetylalkyl group, C1-C20 carboxyl group, C2-C20 alkyl carboxyl group, or C4-C20 cycloalkyl carboxyl group. Claim 8 In paragraph 4, the intermediate layer comprises a silicon-containing monomer having an iodine or phenol group substituent, and the silicon-containing monomer A method for manufacturing a semiconductor device selected from a group consisting of Claim 9 In paragraph 4, the intermediate layer comprises a silicon-containing monomer having an iodine or phenol group substituent, and the silicon-containing monomer comprises a photocatalytic agent substituent, A method for manufacturing a semiconductor device selected from a group consisting of Claim 10 A composition comprising one or more selected from the group consisting of a photogenerator, a chemical radiation absorbing additive having an iodine substituent, and a silicon-containing monomer having an iodine or phenolic substituent, and a silicon-containing material, wherein the photogenerator An anion selected from the group consisting of, and A chemical radiation absorbing additive comprising a cation selected from the group consisting of; and having an iodine substituent, structure I n A composition having -R1, wherein n = 1-10, and R1 is selected from the group consisting of a substituted or unsubstituted C1-C10 alkyl group, C6-C10 aryl group, C1-C10 aralkyl group, C3-C10 cycloalkyl group, C1-C10 hydroxyalkyl group, C2-C10 alkoxyalkyl group, C2-C10 acetyl group, C3-10 acetylalkyl group, C1-C10 carboxyl group, C2-C10 alkyl carboxyl group, C3-C10 cycloalkyl carboxyl group, or adamantyl group; wherein the silicon-containing monomer has the following structure: In the above formula, Z and D are independently substituted or unsubstituted C1-C20 alkyl groups, C3-C20 cycloalkyl groups, C1-C20 hydroxyalkyl groups, C2-C20 alkoxy groups, C3-C20 alkoxyalkyl groups, C2-C20 acetyl groups, C3-C20 acetyl alkyl groups, C1-C20 carboxyl groups, C2-C20 alkyl carboxyl groups, C1-C20 alkyl fluoride groups, C6-C20 aryl groups, C7-C20 aralkyl groups, or adamantyl groups, wherein Z and D independently comprise 1-10 iodine or 1-10 phenolic OH groups, Z is a single bond, and D is H; R4, R5, and R6 are each H or a substituted or unsubstituted C6-C20 aryl group, C7-C20 aralkyl group, C3-C20 cycloalkyl group, C1-C20 hydroxyalkyl group, C2-C20 alkoxy group, C3-C20 alkoxyalkyl group, C2-C20 acetyl group, C3-C20 acetylalkyl group, C1-C20 carboxyl group, C2-C20 alkyl carboxyl group, or C4-C20 cycloalkyl carboxyl group.